Blower, article with ozone-degradable coating film, air conditioning system, ozone decomposition method, and method for forming ozone-degradable film

By providing an ozone decomposition coating film containing manganese oxide catalyst, activated carbon, polyacrylate dispersant and resin in the blower portion of the blower, the problem of ozone decomposition in the atmosphere is solved, and the effect of reducing ozone concentration and reducing photochemical smoke is achieved.

CN113931859BActive Publication Date: 2025-04-04TOYOTA JIDOSHA KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202110720729.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-22
Filing Date
2021-06-28
Publication Date
2025-04-04
Estimated Expiration
2041-06-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively decompose ozone in the atmosphere, resulting in the production of photochemical smoke and affecting the environment and human health.

Method used

A blower is developed, wherein an ozone decomposition coating film is provided on the blower portion, which contains a manganese oxide catalyst, activated carbon, a polyacrylate dispersant and a resin, and the ozone decomposition performance is improved by combining these components.

Benefits of technology

By contacting the air with the ozone decomposition coating, the ozone concentration in the atmosphere is significantly reduced, thereby reducing the generation of photochemical smoke and protecting the environment and human health.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113931859B_ABST
    Figure CN113931859B_ABST
Patent Text Reader

Abstract

The present invention provides a blower, an article with an ozone-degrading coating, an air conditioning system, an ozone-degrading method, and a method for forming an ozone-degrading film. The blower comprises: a blower section that sucks in and delivers air; at least one of a first ventilation member and a second ventilation member, the first ventilation member having a first ventilation hole through which the air delivered from the blower passes, and a coating containing a manganese oxide catalyst, activated carbon, a polyacrylate dispersant, and a resin is provided on the wall surface of the first ventilation hole; and the second ventilation member having a second ventilation hole through which the air sucked into the blower passes, and a coating is provided on the wall surface of the second ventilation hole.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a blower, an article with an ozone-degradable coating film, an air conditioning system, an ozone decomposition method, and a method for forming an ozone-degradable film. Background Art

[0002] Exhaust gas from factories, cars, etc. contains nitrogen oxides (NO x ), carbon oxides (HC), and other volatile organic compounds (VOC). Volatile organic compounds (VOC) are converted into photochemical oxidants (O x ). The photochemical oxidant is an air pollutant with ozone (O3) as its main component, that is, an environmental load substance, and is the cause of photochemical smog.

[0003] In Japan, the environmental standard for photochemical oxidants is set at 0.06 ppm or less per hour. However, the current situation is that the standard value is continuously exceeded, and as global awareness of global environmental protection issues has increased in recent years, measures to reduce photochemical oxidants are expected to be taken immediately.

[0004] Therefore, a technology has been proposed for preventing the generation of photochemical smog by decomposing (ie, purifying) generated ozone while implementing emission restrictions on volatile organic compounds such as nitrogen oxides.

[0005] For example, in some areas of California, the United States, a system for purifying the atmosphere has been developed in which a radiator carrying a catalyst for decomposing ozone is mounted on a vehicle and the vehicle is driven to improve the atmosphere. In addition, a vehicle using direct ozone reduction technology (DOR), for example, a vehicle equipped with an air purification device capable of decomposing ozone in the atmosphere by an ozone decomposition catalyst (i.e., an ozone purification catalyst) has been put into practical use. In particular, in California, the United States, a vehicle that has introduced such direct ozone reduction technology (DOR) or a manufacturer that sells the vehicle is given a predetermined preferential treatment (e.g., NMOG credit certification) that is deemed to have reduced the emission of non-methane organic gases (NMOG) that are substances causing photochemical smog.

[0006] Here, as a technology related to a radiator that loads an ozone decomposition catalyst, for example, Patent Document 1 and Patent Document 2 disclose a technology of a vehicle air purification device that loads a metal oxide catalyst on the surface of a radiator (heat sink, etc.) into which the atmosphere flows while the vehicle is running, and record the situation in which ozone contained in the atmosphere is decomposed by the ozone decomposition catalyst layer on the surface of the radiator.

[0007] Furthermore, Patent Document 3 proposes a vehicle air purification device that uses not only a metal oxide catalyst but also activated carbon having a function of purifying ozone.

[0008] Patent Document 1: Japanese Patent Application No. 2002-514966

[0009] Patent Document 2: Japanese Patent Application Publication No. 2008-000746

[0010] Patent Document 3: Japanese Patent Application Publication No. 2014-024027 Summary of the invention

[0011] Thus, as shown in Patent Documents 1 to 3, a technology of a vehicle air purification device has been developed that purifies ozone in the atmosphere by loading a catalyst that decomposes ozone in the atmosphere on the surface of a radiator (heat sink, etc.) and utilizing an ozone decomposition catalyst layer on the surface of the radiator.

[0012] On the other hand, if a blower such as a fan, circulator, air conditioner, or air purifier has the function of decomposing ozone in the atmosphere and sending out air with reduced ozone concentration, it can make a greater contribution to the purification of ozone in the atmosphere of facilities such as indoors and outdoors.

[0013] For example, many crops and garden crops are highly sensitive to ozone, and ozone causes various damage symptoms to the crops, which can lead to a reduction in growth and harvest. Therefore, a blower with the function of decomposing ozone in the atmosphere can reduce ozone damage to crops and garden crops in indoor and outdoor facilities.

[0014] Furthermore, for example, since the influence of ozone on the human body has been reported, a blower having a function of decomposing ozone in the atmosphere can also reduce the influence of ozone on the human body in facilities such as indoors and outdoors.

[0015] In addition, not limited to blowers, as long as ozone can be decomposed by an object that has the function of decomposing ozone in the atmosphere, an environment with reduced ozone concentration can be achieved, and ozone damage to crops and garden crops and the impact of ozone on the human body can also be reduced.

[0016] Therefore, an object of one aspect of the present disclosure is to provide a blower capable of sending air with a reduced ozone concentration.

[0017] Another aspect of the present disclosure aims to provide an article with an ozone-degradable coating film, an air conditioning system, an ozone decomposing method, and a method for forming an ozone-degradable film, which can realize an environment with a reduced ozone concentration.

[0018] A first aspect of the present disclosure is a blower comprising: a blower section that sucks in and delivers air; an ozone-decomposing coating film that is disposed on at least one of a position contacted by air delivered from the blower section and a position contacted by air sucked into the blower section, and that contains a manganese oxide catalyst, activated carbon, a polyacrylate dispersant, and a resin.

[0019] According to the first embodiment of the present disclosure, since the ozone decomposition coating film containing the above-mentioned components has a high ozone decomposition performance, when the air sent out from the air blowing part contacts the ozone decomposition coating film, the ozone contained in the air will be decomposed. In addition, when the air sucked into the air blowing part contacts the ozone decomposition coating film, the ozone contained in the air will be decomposed. Therefore, the air with a reduced ozone concentration can be sent out.

[0020] The second embodiment of the present disclosure is a blower described in the first embodiment, wherein the blower comprises at least one of a first ventilation component and a second ventilation component, the first ventilation component having a first ventilation hole for passing the air sent out from the blowing section, and the ozone-degrading coating is provided on the wall surface of the first ventilation hole, and the second ventilation component having a second ventilation hole for passing the air sucked into the blowing section, and the ozone-degrading coating is provided on the wall surface of the second ventilation hole.

[0021] According to the second embodiment of the present disclosure, since the ozone decomposition coating film containing the above-mentioned components has a high ozone decomposition performance, when the air sent out from the air blowing part passes through the vent hole of the first ventilation component and contacts the ozone decomposition coating film, the ozone contained in the air will be decomposed. In addition, when the air sucked into the air blowing part passes through the second vent hole of the second ventilation component and contacts the ozone decomposition coating film, the ozone contained in the air will be decomposed. Therefore, the air with a reduced ozone concentration can be sent out.

[0022] Furthermore, a third aspect of the present disclosure is the blower according to the second aspect, wherein the first ventilation member is a honeycomb structure member having through holes as the first ventilation holes.

[0023] According to the third aspect of the present disclosure, by using a honeycomb structure member having a large wall surface area of ​​through holes through which air passes as the first ventilation member, the contact area between air and the ozone decomposing coating film is increased, thereby allowing air with reduced ozone concentration to be delivered.

[0024] Furthermore, a fourth aspect of the present disclosure is the blower according to the second aspect or the third aspect, wherein the second ventilation member is a honeycomb structure member having through holes as the second ventilation holes.

[0025] According to the fourth aspect of the present disclosure, by using a honeycomb structure member having a large wall surface area of ​​through holes through which air passes as the second ventilation member, the contact area between air and the ozone decomposing coating film is increased, thereby allowing air with reduced ozone concentration to be delivered.

[0026] Furthermore, a fifth aspect of the present disclosure is the blower according to any one of the second aspect to the fourth aspect, wherein the first ventilation member is a filter member having mesh holes as the first ventilation holes.

[0027] According to the fifth aspect of the present disclosure, by using a filter member having a large mesh wall area through which air passes as the first ventilation member, the area of ​​contact between air and the ozone decomposing coating is increased, and air with a reduced ozone concentration can be delivered.

[0028] Furthermore, a sixth aspect of the present disclosure is the blower according to any one of the second aspect to the fifth aspect, wherein the second ventilation member is a filter member having mesh holes as the second ventilation holes.

[0029] According to the sixth aspect of the present disclosure, by using a filter member having a large mesh wall area through which air passes as the second ventilation member, the area of ​​contact between air and the ozone decomposing coating film is increased, and air with a reduced ozone concentration can be delivered.

[0030] Furthermore, a seventh aspect of the present disclosure is the blower according to any one of the second aspect to the sixth aspect, wherein the blower unit has a rotary blade having the ozone decomposing coating film provided on a blade surface.

[0031] According to the seventh aspect of the present disclosure, when air is sucked in and sent out by the rotation of the rotary blades, the air is brought into contact with the ozone decomposing coating film, thereby being able to output air with a reduced ozone concentration.

[0032] Furthermore, an eighth aspect of the present disclosure is the blower according to any one of the second aspect to the seventh aspect, further comprising a guide member that guides the air sent out from the blowing unit toward the first ventilation member.

[0033] According to the eighth aspect of the present disclosure, the air flow rate of air passing through the first ventilation hole of the first ventilation member is increased by the guide member, so that the air with a reduced ozone concentration can be sent out.

[0034] Furthermore, a ninth aspect of the present disclosure is the blower according to any one of the first aspect to the eighth aspect, wherein the manganese oxide-based catalyst is a manganese dioxide-based catalyst.

[0035] According to the ninth aspect of the present disclosure, the manganese dioxide-based catalyst has high catalytic activity, thereby improving the ozone decomposition performance of the ozone decomposing coating film, and thereby being able to deliver air with a reduced ozone concentration.

[0036] Furthermore, a tenth aspect of the present disclosure is the blower according to any one of the first to ninth aspects, wherein a blending ratio of the manganese oxide catalyst to the activated carbon is 20 / 80≤activated carbon / manganese oxide catalyst≤80 / 20 in terms of mass ratio.

[0037] According to the tenth aspect of the present disclosure, the ozone decomposition performance of the ozone decomposing coating film is improved by the synergistic effect of ozone decomposition achieved by the combination of the manganese oxide-based catalyst and the activated carbon, and air with a reduced ozone concentration can be delivered.

[0038] Furthermore, an eleventh aspect of the present disclosure is the blower according to any one of the first to tenth aspects, wherein a total amount of the manganese oxide-based catalyst and the activated carbon is 60% by mass to 90% by mass with respect to the ozone decomposing coating.

[0039] According to the eleventh aspect of the present disclosure, high ozone decomposition performance is imparted to the ozone decomposable coating film without impairing the adhesion of the ozone decomposable coating film, and air with a reduced ozone concentration can be continuously sent out.

[0040] In addition, the twelfth aspect of the present disclosure is a blower described in any one of the first to eleventh aspects, wherein the polyacrylate dispersant is a dispersant having a weight average molecular weight in the range of 5000 to 30000, an acid value in the range of 1 to 50, and a hydrogen ion index in the range of pH 4 to pH 9.

[0041] According to the twelfth aspect of the present disclosure, high ozone decomposition performance is imparted to the ozone decomposable coating film without impairing the adhesion of the ozone decomposable coating film, so that air with a reduced ozone concentration can be continuously sent out.

[0042] In addition, the thirteenth aspect of the present disclosure is the blower described in any one of the first to twelfth aspects, wherein the content of the polyacrylate dispersant is in the range of 1.5 to 75 parts by mass relative to 100 parts by mass of the total amount of the manganese oxide catalyst and the activated carbon.

[0043] According to the thirteenth aspect of the present disclosure, high ozone decomposition performance is imparted to the ozone decomposing coating film, so that air with a reduced ozone concentration can be sent out.

[0044] Furthermore, a fourteenth aspect of the present disclosure is the blower according to any one of the first to thirteenth aspects, wherein the resin is at least one selected from a (meth)acrylic resin and a polyacrylic resin.

[0045] According to the fourteenth embodiment of the present disclosure, when a (meth) acrylic resin having excellent adhesion to metal is used, the adhesion of the ozone decomposing coating to metal parts (ventilation parts, rotating blades, guide parts, etc.) is improved, so that air with reduced ozone concentration can be continuously delivered. In addition, when a polyacrylic resin having excellent adhesion to metal and resin is used, the adhesion of the ozone decomposing coating to metal and resin parts (ventilation parts, rotating blades, guide parts, etc.) is improved, so that air with reduced ozone concentration can be continuously delivered.

[0046] In addition, the fifteenth embodiment of the present disclosure is a blower described in any one of the first to fourteenth embodiments, wherein the ozone-decomposing coating is composed of a cured coating of an aqueous coating composition, and the aqueous coating composition contains the manganese oxide catalyst, the activated carbon, the polyacrylate dispersant and the resin, and also contains a solvent with water as the main component and a pH regulator.

[0047] According to the fifteenth aspect of the present disclosure, while suppressing the emission of VOCs and contributing to environmental measures, it is possible to send out air with a reduced ozone concentration.

[0048] Furthermore, a sixteenth aspect of the present disclosure is an article with an ozone-degradable coating film, comprising: an article body; and an ozone-degradable coating film provided on the article body and containing a manganese oxide-based catalyst, activated carbon, a polyacrylate-based dispersant, and a resin.

[0049] According to the sixteenth aspect of the present disclosure, since the ozone decomposing coating film containing the above-mentioned components has high ozone decomposing performance, the ozone contained in the atmosphere is decomposed by bringing the atmosphere into contact with the ozone decomposing coating film provided on the article body, thereby realizing an environment with reduced ozone concentration.

[0050] Furthermore, a seventeenth aspect of the present disclosure is the article with an ozone-degradable coating film according to the sixteenth aspect, wherein the article body is a honeycomb structure member, a filter member, a duct, or a building material.

[0051] According to the seventeenth aspect of the present disclosure, an environment with a reduced ozone concentration can be realized by a honeycomb structure member, a filter member, a duct, or a building material.

[0052] Furthermore, an eighteenth aspect of the present disclosure is an air conditioning system comprising at least one selected from the blower according to any one of the first to fifteenth aspects, and the article with an ozone-degradable coating according to the sixteenth or seventeenth aspect.

[0053] According to the eighteenth aspect of the present disclosure, since ozone contained in the atmosphere is decomposed by the ozone decomposing coating film having high ozone decomposition performance, an environment with a reduced ozone concentration can be realized.

[0054] Furthermore, a nineteenth aspect of the present disclosure is an ozone decomposition method, wherein an ozone decomposing coating film including a manganese oxide-based catalyst, activated carbon, a polyacrylate-based dispersant, and a resin is brought into contact with air to decompose ozone in the air.

[0055] In the nineteenth aspect of the present disclosure, since the ozone decomposing coating film containing the above-mentioned components has high ozone decomposing performance, the ozone contained in the atmosphere is decomposed by bringing the atmosphere into contact with the ozone decomposing coating film, thereby realizing an environment with reduced ozone concentration.

[0056] In addition, the twentieth embodiment of the present disclosure is a method for forming an ozone decomposing film, wherein an aqueous coating composition is applied to an object to be coated and then cured, wherein the aqueous coating composition contains a manganese oxide catalyst, activated carbon, a polyacrylate dispersant, and a resin, and also contains a solvent mainly composed of water and a pH regulator.

[0057] According to the twentieth aspect of the present disclosure, the ozone decomposing coating film formed by the aqueous coating composition containing the above-mentioned components has high ozone decomposition performance, and thus, an environment with reduced ozone concentration can be realized.

[0058] According to one aspect of the present disclosure, it is possible to provide a blower capable of sending out air with a reduced ozone concentration.

[0059] According to another aspect of the present disclosure, it is possible to provide an article with an ozone-degradable coating film, an air conditioning system, an ozone decomposing method, and a method for forming an ozone-degradable film, which can realize an environment with a reduced ozone concentration. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Embodiments of the present disclosure will be described in detail based on the following drawings, in which:

[0061] Figure 1 This is a schematic exploded perspective view showing an example of the blower according to the present embodiment.

[0062] Figure 2 It is a schematic cross-sectional view showing the periphery of a blowing unit of the blower according to the present embodiment.

[0063] Figure 3 It is a schematic plan view showing filter members provided as the first ventilation member and the second ventilation member in the blower according to the present embodiment.

[0064] Figure 4 It is a schematic diagram for explaining the method of the ozone decomposition evaluation test in the test examples and comparative examples shown in Table 1, Table 2, and Table 4.

[0065] Figure 5 It is a schematic diagram for explaining the method of the ozone decomposition evaluation test in the test examples and comparative examples shown in Table 3.

[0066] Figure 6 It is a schematic structural diagram showing an example of a building having an air-conditioning system according to the present embodiment. DETAILED DESCRIPTION

[0067] Hereinafter, an embodiment as an example of the present disclosure will be described.

[0068] In addition, in this specification, the same symbols are attached to components having substantially the same functions throughout all the drawings, and overlapping descriptions may be omitted.

[0069] The numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0070] In the numerical range recorded in stages, the upper limit value recorded in a certain numerical range can also be replaced by the upper limit value of the numerical range recorded in other stages. In addition, in the numerical range recorded in stages, the lower limit value recorded in a certain numerical range can also be replaced by the lower limit value of the numerical range recorded in other stages.

[0071] In the numerical range, the upper limit value or the lower limit value described in a certain numerical range may be replaced with the value shown in the embodiment.

[0072] A plurality of substances corresponding to each component may be included. When there are a plurality of substances corresponding to each component, unless otherwise specified, the content rate or content of each component refers to the total content rate or content of the plurality of substances.

[0073] <Blower>

[0074] Figure 1 This is a schematic exploded perspective view showing an example of the blower according to the present embodiment. Figure 2 It is a schematic cross-sectional view showing the periphery of a blowing unit of the blower according to the present embodiment.

[0075] like Figure 1 as well as Figure 2 As shown, the blower 100 according to the present embodiment includes a blower unit 10 , a first ventilation member 14 , a second ventilation member 16 , a guide member 18 , and a support member 20 .

[0076] The blower 10 is provided, for example, inside the guide member 18, and sucks in and blows air. The blower 10 includes, for example, a rotary blade 12 and a drive motor (not shown) that drives the rotary blade 12 to rotate.

[0077] The rotating blades 12 are not particularly limited as long as they are fans that suck in air and blow it, and can be, for example, well-known fans such as centrifugal fans, axial flow fans, diagonal flow fans, and cross flow fans, depending on the type of the blower 100. Specifically, as the rotating blades 12, well-known fans such as propeller fans, sirocco fans, turbo fans, and linear flow fans (registered trademarks) can be exemplified. In addition, in the present embodiment, a propeller fan is shown as the rotating blade 12.

[0078] An ozone decomposing coating film 22 is provided on the blade surface of the rotary blade 12 .

[0079] The first ventilation member 14 is provided, for example, at one end of the guide member 18 on the downstream side in the blowing direction of the air. Specifically, the first ventilation member 14 is fitted into an outlet of the guide member 18 through which the air sent from the blower 10 is discharged.

[0080] The first ventilation member 14 is composed of, for example, a honeycomb structure member having through holes as first ventilation holes 14A through which the air sent from the blower 10 passes. The honeycomb structure member has a structure in which a plurality of through holes having a hexagonal cross-sectional shape are arranged without gaps inside the frame portion of the edge.

[0081] In the first ventilation member 14 , an ozone decomposing coating film 22 is provided on the wall surface of the first ventilation hole 14A, that is, on the wall surface of the through-hole of the honeycomb structure.

[0082] The second ventilation member 16 is provided, for example, at one end of the guide member 18 on the upstream side in the blowing direction of the air. Specifically, the second ventilation member 16 is fitted into the suction port of the guide member 18 through which the air is sucked by the blower 10, for example.

[0083] The second ventilation member 16 is constituted by, for example, a honeycomb structure member having through holes as second ventilation holes 16A for ventilation of the air sucked into the blowing unit 10. The honeycomb structure member has a structure in which a plurality of through holes having a hexagonal cross-sectional shape are arranged without gaps.

[0084] In the second ventilation member 16 , an ozone decomposing coating film 22 is provided on the wall surface of the second ventilation hole 16A, that is, on the wall surface of the through-hole of the honeycomb structure.

[0085] Guide member 18 is formed of a cylindrical member having an inner diameter larger than an outer diameter of rotary blades 12 of blower unit 10 , and includes blower unit 10 therein.

[0086] The guide member 18 guides the air sent out from the blower 10 to the first ventilation member 14. The guide member also serves as a guide member for guiding the air passing through the second ventilation holes 16A of the second ventilation member 16 to the blower 10.

[0087] An ozone-degradable coating film 22 is provided on the inner wall surface of the guide member 18 .

[0088] Support member 20 supports guide member 18 on which blower unit 10 is provided, for example.

[0089] The support member 20 is constituted by a tripod, for example. The support member 20 is not limited to a tripod, and may be constituted by a well-known support member including a base, and one or more columnar bodies or plate-like bodies extending from the base and movably fixing the guide member at one end.

[0090] The ozone decomposing coating film 22 contains a manganese oxide-based catalyst, activated carbon, a polyacrylate-based dispersant, and a resin.

[0091] The ozone decomposing coating film 22 is provided at least on the wall surface of the first ventilation hole 14A of the first ventilation member 14 , the wall surface of the second ventilation hole 16A of the second ventilation member 16 , and the blade surface of the rotary blade 12 .

[0092] However, from the viewpoint of being able to efficiently deliver air with reduced ozone concentration in the blower 100, it is preferred that a coating having high ozone decomposition performance is provided at a portion including the walls of each vent hole of the first ventilation component and the second ventilation component of the blower and the portion with which the inhaled air contacts until the air is discharged.

[0093] The ozone decomposable coating film 22 will be described in detail later.

[0094] The blower 100 according to the present embodiment described above includes an ozone decomposing coating 22, which is provided on the wall surfaces of the first vent hole 14A of the first vent member 14 and the second vent hole 16A of the second vent member 16, and contains a manganese oxide catalyst, activated carbon, a polyacrylate dispersant, and a resin. The ozone decomposing coating 22 has a high ozone decomposition performance due to the above components.

[0095] In the blower 100, the air sent out from the blowing unit 10 contacts the ozone decomposing coating 22 when passing through the first vent hole 14A of the first ventilation member 14. As a result, the ozone contained in the air is decomposed. Therefore, in the blower 100, the air with reduced ozone concentration can be sent out.

[0096] In blower 100, air sucked into the blowing unit contacts ozone decomposing coating 22 when passing through second vent holes 16A of second ventilation member 16. Ozone contained in the air is thereby decomposed. Therefore, blower 100 can deliver air with reduced ozone concentration.

[0097] In particular, since the blower 100 includes both the first ventilation member 14 and the second ventilation member 16 provided with the ozone decomposing coating film 22 , it is possible to send out air with a further reduced ozone concentration.

[0098] In addition, the blower 100 may be a mode that includes at least one of the first ventilation member 14 and the second ventilation member 16 provided with the ozone decomposable coating film 22. In addition, the blower 100 may be any one of (1) a mode that includes the first ventilation member 14 provided with the ozone decomposable coating film 22 and the second ventilation member 16 not provided with the ozone decomposable coating film 22, and (2) a mode that includes the first ventilation member 14 not provided with the ozone decomposable coating film 22 and the second ventilation member 16 provided with the ozone decomposable coating film 22.

[0099] However, from the viewpoint of sending out air with a further reduced ozone concentration, it is preferable that the blower 100 is provided with at least the first ventilation member 14 provided with the ozone decomposing coating film 22 .

[0100] In the blower 100, the first ventilation member 14 and the second ventilation member 16 are formed of a honeycomb structure member. In the honeycomb structure member, the wall surface area of ​​the through hole through which air passes is large. That is, the area coated with the ozone decomposing coating 22 is large, so that the area in contact with the ozone decomposing coating 22 when the air passes through the through hole is also increased. Therefore, the air with a reduced ozone concentration can be further delivered.

[0101] Here, the first ventilation element 1 can be as follows Figure 3 As shown, the filter member is constituted by, for example, a filter member having mesh holes as first air holes 14A through which the air sent out from blower 10 passes.

[0102] Likewise, the second ventilation member 16 may also be Figure 3 As shown, for example, the filter member is composed of a filter member having mesh holes as second air holes 16A through which the air sucked into the blower 10 passes.

[0103] As the filter member, for example, a well-known filter such as a fiber filter (a fabric filter, a nonwoven filter, etc.), a metal filter, a ceramic filter, a resin filter (including a foamed resin filter), etc. can be used.

[0104] The filter member may be any one of a coarse dust filter, a medium performance air filter, a HEPA (High Efficiency Particulate Air Filter) filter, and a ULPA (Ultra Low Penetration Air Filter) filter, depending on the purpose.

[0105] The filter component may also be composed of a plurality of filters having different functions.

[0106] The ozone decomposing coating film 22 is also provided on the wall surface of the mesh of the filter member.

[0107] In the filter member, the area of ​​the wall surface of the mesh through which air passes is large. That is, the area coated with the ozone decomposing coating 22 is large, and the area where the air passing through the mesh contacts the ozone decomposing coating 22 is also large.

[0108] Therefore, the blower 100 including the filter members as the first ventilation member 14 and the second ventilation member 16 can also send out air in which the ozone concentration is further reduced.

[0109] However, the pressure loss of air passing through the honeycomb structure member is smaller than that of the filter member. Therefore, the blower 100 including the honeycomb structure member as the first ventilation member 14 and the second ventilation member 16 reduces the pressure loss and can efficiently deliver air with reduced ozone concentration.

[0110] In addition, the following method may be adopted, that is, one of the first ventilation member 14 and the second ventilation member 16 is a honeycomb structure member, and the other is a filter member. Compared with the method in which both the first ventilation member 14 and the second ventilation member 16 are honeycomb structure members, this method has the advantage of achieving both cost reduction and weight reduction of the blower 100. Moreover, in this method, it is sufficient to provide an ozone decomposing coating film on at least one of the honeycomb structure member and the filter member.

[0111] In addition, the first ventilation component 14 and the second ventilation component 16 are not limited to honeycomb structure components or filter components, and may be, for example, (1) a structural component in which a plurality of through holes having a circular or polygonal (triangular, quadrilateral, etc.) cross-sectional shape are arranged as the first ventilation hole 14A and the second ventilation hole 16A, (2) a structural component in which a plurality of straight or curved heat sinks are arranged in a radial or vortex form from the center, and the gaps between adjacent heat sinks are set as the first ventilation hole 14A and the second ventilation hole 16A, etc.

[0112] The blower 100 includes a rotary blade 12 provided with an ozone decomposing coating 22. The rotation of the rotary blade 12 causes the air to contact the ozone decomposing coating 22 when the air is sucked in and sent out. Therefore, the blower 100 can send out air with a further reduced ozone concentration.

[0113] The blower 100 includes a guide member 18 that guides the air sent out from the blower 10 toward the first ventilation member 14 .

[0114] The guide member 18 can suppress the sent air from being drawn out from the periphery of the first ventilation member 14 and increase the ventilation amount of the air passing through the first ventilation holes 14A of the first ventilation member 14 .

[0115] Therefore, air with a reduced ozone concentration can be efficiently delivered.

[0116] Furthermore, the ozone decomposing coating film 22 is also provided on the inner wall of the guide member 18. Therefore, the blower 100 can send out air in which the ozone concentration is further reduced.

[0117] The blower 100 is not particularly limited as long as it is a device capable of sending out air, and well-known blowers such as electric fans, circulators, air conditioners, air cleaners, radiator fans, and ventilation devices are used. In addition, the blower 100 may also be a so-called bladeless electric fan blower having a body having a blower part and an inlet and an annular member having a slit for discharging the air sent out from the blower part.

[0118] There is no limitation on the installation method of the blower 100, and blowers of well-known installation methods such as floor-standing type, desktop type, ceiling-mounted type, sidewall-mounted type, and outdoor installation type are adopted.

[0119] Furthermore, in blower 100 , first ventilation member 14 may be interposed on the path until air is discharged from blower 10 . On the other hand, second ventilation member 16 may be interposed on the path until air is sucked into blower 10 .

[0120] Here, in the blower 100 , the ozone decomposing coating film 22 is not limited to the one provided on the first ventilation member 14 , the second ventilation member 16 , the rotary blade 12 , and the guide member 18 .

[0121] The ozone-degradable coating film 22 may be provided at least on one of a position contacted by the air delivered from the blower 10 and a position contacted by the air sucked into the blower 10. Specifically, for example, the ozone-degradable coating film 22 may be provided on at least one of a component constituting the air suction passage of the blower 100 and a component constituting the air exhaust passage of the blower 100.

[0122] Thus, the blower 100 can send out air with a reduced ozone concentration.

[0123] <Articles with ozone-degradable coating>

[0124] The article with an ozone-degradable coating film according to the present embodiment includes an article body and an ozone-degradable coating film provided on the article body and containing a manganese oxide-based catalyst, activated carbon, a polyacrylate-based dispersant, and a resin.

[0125] The ozone-degradable coating film is provided on at least a portion of the surface of the article body that is in contact with the atmosphere. The ozone-degradable coating film will be described in detail later.

[0126] On the other hand, representative examples of the articles on which the ozone decomposing coating film is provided include honeycomb structure parts, filter parts, ducts, and construction materials.

[0127] As the honeycomb structural member, the honeycomb structural member described in the blower according to the present embodiment is exemplified. In addition, at least an ozone decomposing coating film is provided on the inner wall surface of the through-hole of the honeycomb structural member.

[0128] As the filter member, the filter member described in the blower according to the present embodiment is exemplified. In addition, at least an ozone decomposing coating film is provided on the wall surface of the mesh of the filter member.

[0129] The honeycomb structure components and filter components with ozone-degradable coatings are installed, for example, on the air suction part of a blower (well-known blowers such as fans, circulators, air conditioners, air purifiers, radiator fans, and ventilation fans), the air exhaust part of a blower, the outdoor unit of an air conditioner, the air exhaust part of a virus removal device using ozone, the air exhaust part of a copier, the air exhaust part of a printer, etc.

[0130] Examples of the duct include well-known ducts such as metal ducts, resin ducts, cylindrical ducts, polygonal cylindrical ducts, and flexible ducts. For example, at least an ozone decomposing coating film is provided on the inner wall surface of the duct.

[0131] The duct with the ozone decomposing coating is disposed as, for example, an air supply duct, an exhaust duct, an air circulation duct, or the like of an air conditioning system.

[0132] Examples of building materials include well-known materials such as interior wall materials, exterior wall materials, roof materials, floor materials, ceiling materials, screen doors, windows, plastic films for plastic greenhouses, curtains, fences, etc. Furthermore, for example, at least an ozone decomposing coating film is provided on the exposed surface of the building material.

[0133] Examples of the article body on which the ozone-degradable coating film is provided include, in addition to the above, parts of a blower, parts of a virus removal device using ozone, parts of a copy machine, parts of a printer, or agricultural materials.

[0134] As components of a virus removal device, a copy machine, or a printer using ozone, there can be exemplified components constituting an air exhaust unit.

[0135] As components of the blower, examples include the ventilation components described in the blower involved in the above-mentioned embodiment, the rotating blades (fan), the guide components, the components constituting the air suction passage of the blower, the air exhaust passage of the blower, the components constituting the outdoor unit of the air conditioner, etc.

[0136] Examples of agricultural materials include films or nets, bags (vegetable bags, fruit bags, etc.) for weed control, insect repellent, photosynthesis promotion, windbreak, heat insulation, and the like.

[0137] By placing the articles with ozone-degradable coatings according to the present embodiment described above in accordance with the purpose of each article, the ozone-degradable coatings are brought into contact with the atmosphere to decompose ozone in the atmosphere, thereby achieving an environment with reduced ozone concentration.

[0138] <Air conditioning system>

[0139] Figure 6 This is a schematic structural diagram showing an example of a building having an air-conditioning system according to the present embodiment.

[0140] The building 300 includes, for example, a patio room 304A, a first room 304B, and a second room 304C that are partitioned by partition walls 302A and 302B.

[0141] The air conditioning system of the building 300 includes, for example, a heat exchange type ventilator 30 provided in the attic room 304A and having a fan (not shown), an air supply duct 32A, an exhaust duct 32B, and an air supply filter member 34 .

[0142] The air supply duct 32A is, for example, an air supply duct for supplying air from the outside of the building 300 to the first room 304B, and is connected to the ventilator 30 .

[0143] The exhaust duct 32B is a duct for exhausting air from the second room 304C to the outside of the building 300 , and is connected to the ventilator 30 .

[0144] The air supply filter member 34 is a filter that purifies the air supplied from the air supply duct 32A, and is interposed in the middle of the route of the air supply duct 32A.

[0145] The ventilator 30 supplies air from outside the building 300 to the first room 304B through the air supply duct 32A, and exhausts air from the second room 304C to the outside of the building 300 through the exhaust duct 32B, thereby performing air conditioning in each room of the building 300 .

[0146] The air conditioning system included in the building 300 includes, for example, an air conditioner 36 provided with a filter member (not shown) installed in the first room 304B, wallpaper 38 , and a ceiling material 40 .

[0147] The air conditioning system included in the building 300 includes, for example, wallpaper 38 and ceiling material 40 installed in the second room 304C.

[0148] In the air conditioning system involved in this embodiment, an ozone decomposing coating (not shown) containing a manganese oxide catalyst, activated carbon, a polyacrylate dispersant and a resin is provided on the surface of the fan of the ventilation device 30, the inner wall surface of the air supply duct 32A, the surface of the air supply filter component 34, the surface of the filter component of the air conditioner 36, the surface of the wallpaper 38 and the surface of the ceiling material 40.

[0149] Therefore, the air supplied through the ventilator 30 contacts the surface of the fan of the ventilator 30, the inner wall surface of the air supply duct 32A, and the ozone decomposing coating on the surface of the air supply filter member 34, thereby reducing the ozone concentration.

[0150] Furthermore, the air sent out by the air conditioner 36 comes into contact with the ozone decomposing coating film provided on the surface of the filter member, thereby reducing the ozone concentration.

[0151] In addition, the air existing in the first room 304B and the second room 304C contacts the ozone decomposing coating film provided on the surface of the wallpaper 38 and the surface of the ceiling material 40, thereby reducing the ozone concentration. In addition, when a virus removal device using ozone is arranged in the first room 304B, the ozone generated when removing the virus can be effectively decomposed.

[0152] In the air conditioning system according to the present embodiment described above, since ozone in the air can be decomposed by bringing the air into contact with the ozone decomposing coating film, an environment with a reduced ozone concentration can be realized.

[0153] The air conditioning system according to the present embodiment is not limited to the above-described configuration, and may be an air conditioning system including at least one selected from the blower according to the present embodiment and the article with an ozone-decomposing coating according to the present embodiment.

[0154] Specifically, for example, an air conditioning system provided in a plastic greenhouse and including the blower according to the present embodiment and a plastic film with an ozone decomposing coating for the plastic greenhouse can be exemplified.

[0155] In addition, an air conditioning system can also be illustrated in which a sterilization chamber has the items involved in the above-mentioned present embodiment (for example, components constituting the air exhaust portion in the virus removal device (filter components, etc.), wall materials of the sterilization chamber), and the sterilization chamber has a virus removal device that uses ozone to sterilize viruses on medical instruments such as surgical scalpels.

[0156] Another example is an air conditioning system having the articles according to the present embodiment (for example, the blower according to the present embodiment and the wall material of the storage room) in a storage room for storing medical instruments sterilized in a sterilization room.

[0157] <Ozone decomposition method>

[0158] The ozone decomposition method according to the present embodiment is a method of decomposing ozone in the atmosphere by bringing an ozone-decomposing coating film including a manganese oxide-based catalyst, activated carbon, a polyacrylate-based dispersant, and a resin into contact with the atmosphere.

[0159] Specifically, in the ozone decomposition method according to the present embodiment, for example, one selected from the blower according to the present embodiment and the article with an ozone decomposition coating according to the present embodiment is used to bring the ozone decomposition coating into contact with the atmosphere, thereby decomposing ozone in the atmosphere. More specifically, for example, the air conditioning system according to the present embodiment is used to bring the ozone decomposition coating into contact with the atmosphere, thereby decomposing ozone in the atmosphere. Therefore, the ozone decomposition method according to the present embodiment can achieve an environment in which the ozone concentration is reduced.

[0160] <Coating>

[0161] Hereinafter, the ozone decomposable coating film 22 (hereinafter also referred to as “coating film”) will be described. However, the description will be made by omitting reference numerals.

[0162] The coating film comprises a manganese oxide catalyst, activated carbon, a polyacrylate dispersant, and a resin. Specifically, from the viewpoint of suppressing the emission of VOCs and being able to contribute to environmental measures, it is preferred that the coating film is composed of a cured coating film of an aqueous coating composition (hereinafter, also referred to as a "coating composition"), wherein the aqueous coating composition comprises a manganese oxide catalyst, activated carbon, a polyacrylate dispersant, and a resin, and also comprises a solvent mainly composed of water and a pH regulator.

[0163] The ozone decomposing coating film contains the above-mentioned components, thereby having high ozone decomposing performance. The reason is as follows.

[0164] The manganese oxide catalyst and activated carbon contained in the coating film are both components having ozone decomposition performance.

[0165] When a manganese oxide catalyst and activated carbon are used together as components having ozone decomposition performance, higher ozone decomposition performance can be obtained compared to the case where these components are used alone. Although the reason is not necessarily clear, for example, based on the following reasons (1) to (4), it is believed that the ozone decomposition performance is improved compared to the case where only one of the manganese oxide catalyst or activated carbon is used.

[0166] (1) The ozone catalytic reaction of the manganese oxide catalyst is promoted by the reaction heat of activated carbon and ozone.

[0167] (2) By using a manganese oxide catalyst and activated carbon together, ozone decomposition performance can be achieved over a wider temperature range.

[0168] (3) The manganese oxide-based catalyst enters the pores of the activated carbon, and the activated carbon and the manganese oxide-based catalyst come into contact with ozone efficiently.

[0169] (4) The manganese oxide catalyst prevents oxidation and consumption of activated carbon caused by active oxygen and the like.

[0170] On the other hand, in order to improve the ozone decomposition performance of the coating film, the manganese oxide catalyst and the activated carbon need to be mixed together with good dispersibility. Therefore, in the coating composition for forming the coating film, the manganese oxide catalyst and the activated carbon have high dispersibility, and the coating composition needs to have long-term storage properties, that is, storage stability, in order to maintain the dispersibility.

[0171] When activated carbon is used alone as a component having ozone decomposition performance, it is difficult to ensure the stability of the paint by using a predetermined blending amount of activated carbon to obtain the desired ozone decomposition performance, because the activated carbon adsorbs the resin components (i.e., organic matter) of the paint and agglomerates them due to its adsorption characteristics.

[0172] However, since the amount of activated carbon is reduced by using activated carbon and a manganese oxide catalyst together, both the ozone decomposition performance of the coating film and the storage stability of the coating composition can be satisfied. In addition, the life of the ozone decomposition performance can be extended compared to the case where activated carbon is used alone.

[0173] Furthermore, manganese oxide catalysts are expensive. If the manganese oxide catalyst is used alone, the cost will increase. However, since activated carbon is available at a low price, the cost can be suppressed by using the manganese oxide catalyst and activated carbon together.

[0174] Here, the manganese oxide catalyst and activated carbon having ozone decomposition performance are in the form of granular powder. In order to make the powdered manganese oxide catalyst and activated carbon into a paint, the manganese oxide catalyst and activated carbon need to be uniformly dispersed in the components such as resin and solvent constituting the paint composition.

[0175] However, manganese oxide catalysts and activated carbon, which have large surface areas and can adsorb a large amount of ozone, are prone to agglomeration. In particular, since activated carbon has pores, the resin (i.e., organic matter) and manganese oxide catalysts, which are components of the coating composition, are attached to the pores. As a result, agglomeration is likely to occur.

[0176] When the dispersibility of manganese oxide catalyst and activated carbon is low and the aggregation is large, aggregation and gelation and increase in viscosity will occur, making it difficult to apply the coating. In addition, during application, the piping, pump, etc. of the coating device are easily blocked. In addition, even if the coating can be applied, the coating film will have a granular and rough feel. When applied to cover the substrate, the film thickness of the coating film will become thicker, and the coating film will lack film-forming properties and adhesion and have poor appearance.

[0177] When the manganese oxide catalyst and activated carbon have low dispersibility and high agglomeration, the amount of ozone adsorbed is also small, so that the coating film cannot obtain high ozone decomposition performance. Of course, when the manganese oxide catalyst and activated carbon have low dispersibility and high agglomeration, the storage stability of the coating composition is also lacking due to agglomeration gelation and increase in viscosity, and it is difficult to store for a long time.

[0178] Therefore, when the powdered manganese oxide catalyst and activated carbon are made into a paint, it is preferable to highly disperse the manganese oxide catalyst and activated carbon in order to prevent aggregation of the catalyst and activated carbon.

[0179] In contrast, when a polyacrylate dispersant is blended with a manganese oxide catalyst and activated carbon, the manganese oxide catalyst and activated carbon can be prevented from agglomerating (i.e., deagglomerating) even in a coating composition containing a resin, thereby making it possible to finely and highly disperse the manganese oxide catalyst and activated carbon in the coating composition. In addition, the dispersion stability thereof can be improved.

[0180] It is believed that the high dispersion and dispersion stability of the manganese oxide catalyst and activated carbon achieved by the polyacrylate dispersant is caused, for example, by (1) adsorption caused by electrical repulsion of the manganese oxide catalyst and activated carbon by the polyacrylate dispersant, and (2) steric hindrance caused by the anchor group or polymer chain of the polyacrylate. In other words, it is believed that the manganese oxide catalyst and activated carbon are prevented from aggregating (i.e., deaggregating) by the adsorption and steric hindrance caused by the polyacrylate dispersant, thereby stabilizing the manganese oxide catalyst and activated carbon with a finer particle size.

[0181] In particular, polyacrylate dispersants are high molecular weight and have multiple adsorption sites. Therefore, polyacrylate dispersants are adsorbed on manganese oxide catalysts and activated carbon even at low concentrations, and can achieve high dispersion of manganese oxide catalysts and activated carbon, thereby eliminating the need to use them at high concentrations. As a result, polyacrylate dispersants are less likely to hinder the adsorption of ozone onto manganese oxide catalysts and activated carbon.

[0182] Therefore, the manganese oxide catalyst and activated carbon can be fully deagglomerated and stabilized in the coating composition by the polyacrylate dispersant, that is, the manganese oxide catalyst and activated carbon can be finely and highly dispersed.

[0183] For example, the dispersion of the manganese oxide catalyst and activated carbon in the coating composition measured by a fineness meter (specifically, a fineness meter in accordance with JIS K 5600 and JIS K 5400 (1990)) can be made to have a maximum particle diameter (Dmax) of 20 μm or less by the linear method.

[0184] Furthermore, the 90% cumulative particle diameter (D90) on a volume basis measured by laser analysis (specifically, laser analysis using a laser diffraction particle size distribution measuring device) in the manganese oxide catalyst and activated carbon in the coating composition can be made 10 μm or less.

[0185] Furthermore, the coating film formed by the coating composition in which the manganese oxide catalyst and activated carbon are highly dispersed into fine particles in this way exhibits high ozone decomposition performance because the manganese oxide catalyst and activated carbon are well dispersed and the ozone adsorption amount achieved by the manganese oxide catalyst and activated carbon becomes high. In addition, the granularity and roughness of the coating film are suppressed, and excellent film forming properties and adhesion to the substrate are ensured. Moreover, the smoothness of the coating film is good, and a good coating film appearance is also obtained.

[0186] In addition, since the manganese oxide-based catalyst and activated carbon have high dispersion stability and do not reaggregate, the coating composition using the polyacrylate-based dispersant also has high storage stability and can be stored for a long period of time.

[0187] As described above, the coating film containing the above components has high ozone decomposition performance.

[0188] Hereinafter, the coating film will be described in detail.

[0189] (Manganese oxide catalyst / activated carbon)

[0190] The manganese oxide catalyst decomposes ozone and converts it into oxygen by (1) adsorbing ozone, (2) reducing the activation energy of the self-decomposition reaction of ozone, and (3) decomposing and eliminating ozone. Thus, ozone can be purified and rendered harmless.

[0191] On the other hand, activated carbon converts ozone into carbon monoxide, carbon dioxide (carbon dioxide), active oxygen, oxygen, etc. through (1) adsorption of ozone to pores, (2) reaction between ozone adsorbed on activated carbon and activated carbon, or electron transfer from activated carbon to ozone (i.e., reduction in activation energy of self-decomposition reaction of ozone). Thus, ozone can be purified and rendered harmless.

[0192] In particular, manganese oxide catalysts are most active in a high temperature range (eg, around 80° C.), whereas activated carbon is highly active in a wide temperature range including room temperature (15 to 25° C.) and in a high humidity environment.

[0193] In this way, the coating film including the manganese oxide-based catalyst and the activated carbon can decompose and purify ozone.

[0194] -Manganese oxide catalysts-

[0195] As manganese oxide (Mn x O y )-type catalysts, for example, manganese monoxide (MnO)-type catalysts, manganese dioxide (manganese (IV) oxide)-type catalysts, spinel-type manganate metal catalysts, etc. are listed.

[0196] Among them, the manganese oxide catalyst is preferably a manganese dioxide (MnO2) catalyst, which has high catalytic activity and improves the ozone decomposition performance of the coating. In addition, in general, since the manganese oxide called manganese dioxide is an indefinite compound, in fact, MnO x (x=1.93~2) degree combination.

[0197] Here, manganese dioxide may be any one of natural manganese dioxide, manganese dioxide produced by electrolysis or chemical synthesis, amorphous manganese dioxide, and manganese dioxide having a crystalline structure. Although the crystal structure of manganese dioxide includes, for example, α-type, β-type, γ-type, and δ-type, α-manganese dioxide (manganese dioxide in the form of cryptomelane) is more preferred. In addition, manganese dioxide may also be manganese dioxide having an amorphous structure.

[0198] The manganese oxide-based catalyst may be a catalyst based on manganese oxide (eg, MnO 2 ) and containing a promoter such as NiO, CuO, or AgO as a promoter.

[0199] The manganese oxide-based catalyst may be a catalyst containing calcium oxide or the like that adsorbs moisture.

[0200] However, the manganese oxide-based catalyst is preferably a catalyst having a manganese oxide content of preferably 70% or more, and more preferably 80% or more.

[0201] The specific surface area of ​​the manganese oxide catalyst measured by the BET method using N2 adsorption is preferably 100 m 2 / g~400m 2 / g.

[0202] When the specific surface area is 400m 2 When the catalyst is less than 100 μg / g, the agglomeration of the catalyst is suppressed, and the dispersibility and dispersion stability of the catalyst in the coating composition are improved. When the dispersibility and dispersion stability of the catalyst are improved, in the coating film, the catalyst dispersibility is well blended, thereby improving the ozone decomposition performance of the coating film. In addition, when the dispersibility of the catalyst is improved, it is difficult to cause the clogging of the coating device of the coating composition and it is difficult to produce the coating particle feeling (i.e., agglomerate) on the surface of the coating film, thereby improving the film-forming property and adhesion of the coating film. In addition, the lack of coating film and the peeling off of the catalyst are suppressed. In addition, when the dispersion stability of the catalyst is improved, the storage stability of the coating composition becomes high.

[0203] On the other hand, when the specific surface area is 100m 2 When the content of ozonolysis agent is 1.0447 W / g or more, the ozone decomposition performance of the coating film becomes higher.

[0204] Therefore, when the specific surface area measured by the BET method using N2 adsorption is 100m 2 / g~400m 2 When the manganese oxide catalyst is within the range of 0.1% to 0.1% / g, the film-forming property and adhesion of the coating film are good, the catalyst is unlikely to fall off, and a high ozone decomposition performance can be obtained more effectively and continuously. In addition, good storage stability of the coating composition can be obtained.

[0205] The specific surface area of ​​the manganese oxide catalyst is more preferably 150 m 2 / g~350m 2 / g, more preferably 180m 2 / g~300m 2 / g.

[0206] The median diameter (average particle diameter) of the manganese oxide-based catalyst is preferably 1 μm to 20 μm.

[0207] When the median diameter is 20 μm or less, the specific surface area of ​​the catalyst is large, and the ozone decomposition performance of the coating film is further improved. In addition, the film forming property and adhesion of the coating film are also improved, making it difficult for the coating film to peel off and the catalyst to fall off.

[0208] On the other hand, when the median diameter is more than 1 μm, the dispersibility and dispersion stability of the catalyst in the coating composition will be improved. When the dispersibility and dispersion stability of the catalyst are improved, the catalyst dispersibility in the coating film is well blended, thereby improving the ozone decomposition performance of the coating film. In addition, when the dispersibility of the catalyst is improved, it will be difficult to cause the clogging of the coating device of the coating composition and it will be difficult to produce a coating particle feeling (i.e., agglomerate) on the surface of the coating film, thereby improving the film-forming property and adhesion of the coating film. In addition, the lack and peeling of the coating film and the falling off of the catalyst are suppressed. In addition, when the dispersion stability of the catalyst is improved, the storage stability of the coating composition becomes high.

[0209] Therefore, when a manganese oxide catalyst having a median diameter (average particle diameter) in the range of 1 μm to 20 μm is used, the film-forming property and adhesion of the coating are good, so that the catalyst is unlikely to fall off, and a high ozone decomposition performance can be obtained more effectively and continuously. In addition, good storage stability of the coating composition can be obtained.

[0210] The median diameter (average particle diameter) of the manganese oxide-based catalyst is more preferably 3 μm to 18 μm, and further preferably 5 μm to 15 μm.

[0211] Thus, when using a particle having a median diameter (average particle diameter) in the range of 1 μm to 20 μm and a specific surface area measured by the BET method in the range of 100 to 400 m 2 In the case of a manganese oxide-based catalyst within the range of 0.1 wt. % to 0.1 wt. % / g, the catalyst can be blended in the coating film with good dispersibility, thereby achieving high ozone decomposition performance.

[0212] -Activated carbon-

[0213] Examples of activated carbon include those made from sawdust, wood chips, charcoal, bamboo charcoal, coal (lignite, brown coal, bituminous coal), petroleum (petroleum asphalt, petroleum carbon, etc.), walnut charcoal, palm shell charcoal, resins (phenolic resins, epoxy resins, etc.), rayon, etc.

[0214] The activated carbon may be, for example, activated carbon supported with an organic metal complex having cobalt, iron, or the like as a central metal.

[0215] Among them, preferred activated carbons are palm shell activated carbon, petroleum pitch activated carbon, wood-based activated carbon, etc., which have a very high ozone adsorption specific surface area, and preferably palm shell activated carbon with a carbon ratio of more than 90% and made from coconut trees, oil palm, sago palm trees, etc., which have a relatively high carbon content.

[0216] The specific surface area of ​​the activated carbon measured by the BET method of N2 adsorption is preferably 500 m 2 / g~3000m 2 / g.

[0217] When the specific surface area is 3000m 2 / g or less, the aggregation of activated carbon will be suppressed, and the dispersibility and dispersion stability of the activated carbon in the coating composition will be improved. When the dispersibility and dispersion stability of the activated carbon are improved, the activated carbon will be well dispersed in the coating film, thereby improving the ozone decomposition performance of the coating film. In addition, when the dispersibility of the activated carbon is improved, it is difficult to cause clogging of the coating device of the coating composition, and it is difficult to produce a coating particle feeling (i.e., agglomerates) on the surface of the coating film, thereby improving the film-forming property and adhesion of the coating film. In addition, the lack and peeling of the coating film and the shedding of the activated carbon are suppressed. In addition, when the dispersion stability of the activated carbon is improved, the storage stability of the coating composition becomes high.

[0218] On the other hand, when the specific surface area is 500m 2 When the content of ozone is greater than 50%, the ozone decomposition performance of the coating film will be further improved.

[0219] Therefore, when the specific surface area measured by BET method using N2 adsorption is around 500 m 2 / g~3000m 2 When the activated carbon is within the range of 100 g / cm2, the film-forming property and adhesion of the coating film are good, the catalyst is unlikely to fall off, and a high ozone decomposition performance can be obtained more effectively and continuously. In addition, good storage stability of the coating composition can be obtained.

[0220] The specific surface area of ​​activated carbon is more preferably 600 m 2 / g~2500m 2 / g or less, more preferably 900m 2 / g~2000m 2 / g or less.

[0221] The total pore volume of activated carbon is preferably 0.1 cm2 by calculation based on the nitrogen adsorption amount when the relative pressure P / P0 is 1.0 on the nitrogen BET adsorption isotherm. 3 / g~1.5cm 3 / g, more preferably 0.2 cm 3 / g~1.0cm 3 / g.

[0222] In addition, from the perspective of ozone adsorption performance and prevention of clogging caused by particulate matter in the atmosphere, the average pore size of activated carbon (average pore size calculated by total pore volume / BET specific surface area × 4) is preferably 0.3 to 10 nm, more preferably 0.5 to 5 nm.

[0223] The median diameter (average particle diameter) of the activated carbon is preferably 1 μm to 20 μm.

[0224] When the median diameter is 20 μm or less, the specific surface area of ​​the activated carbon increases, and the ozone decomposition performance of the coating film further increases. In addition, the film-forming property and adhesion of the coating film are also improved, so that the coating film peeling and the activated carbon fall-off are less likely to occur.

[0225] On the other hand, when the median diameter is 1 μm or more, the dispersibility and dispersion stability of the activated carbon in the coating composition are improved. When the dispersibility and dispersion stability of the catalyst are improved, the activated carbon in the coating film is well dispersed and blended, thereby improving the ozone decomposition performance of the coating film. In addition, when the dispersibility of the activated carbon is improved, it is difficult to cause clogging of the coating device of the coating composition, and it is difficult to produce a coating particle feeling (i.e., agglomerates) on the surface of the coating film, thereby improving the film-forming property and adhesion of the coating film. In addition, the lack and peeling of the coating film and the shedding of the activated carbon are suppressed. In addition, when the dispersion stability of the activated carbon is improved, the storage stability of the coating composition becomes high.

[0226] Therefore, when activated carbon having a median diameter (average particle diameter) in the range of 1 μm to 20 μm is used, the film-forming property and adhesion of the coating are good, so that the activated carbon is unlikely to fall off, and a high ozone decomposition performance can be obtained more effectively and continuously. In addition, good storage stability of the coating composition can be obtained.

[0227] The median diameter (average particle diameter) of the activated carbon is more preferably 3 μm to 18 μm, and further preferably 5 μm to 15 μm.

[0228] Thus, by using a particle having a median diameter (average particle diameter) in the range of 1 μm to 20 μm and a specific surface area measured by the BET method in the range of 500 to 3000 m 2 / g of activated carbon, so that the activated carbon can be blended in the coating film with particularly good dispersibility, so that the coating film can obtain high ozone decomposition performance.

[0229] -Method for measuring specific surface area of ​​manganese oxide catalyst and activated carbon-

[0230] The "specific surface area" is the specific surface area measured by the BET method of N2 adsorption. The BET (Brunauer-Emmett-Teller) method is a method of adsorbing molecules with a known adsorption area on the particle surface at the temperature of liquid nitrogen and calculating the specific surface area of ​​the sample based on the amount, and is a method of calculating the specific surface area by low-temperature physical adsorption of nitrogen.

[0231] -Method for measuring median diameter (average particle diameter) of manganese oxide catalyst and activated carbon-

[0232] "Median diameter" refers to the definition of terms in the text and explanation of JIS Z 8901 "Test powders and test particles". In the particle size distribution of powder, the number (or mass) of particles larger than a certain diameter accounts for 50% of the total number of powders, that is, the particle size of 50% of the oversized particles, usually refers to the median diameter or 50% particle diameter, and is expressed as D50.

[0233] Although the average particle diameter and median diameter are used to represent the size of a particle group in terms of definition, in this specification, the "median diameter" is defined as a value indicated in a product description or measured by a laser diffraction / scattering method. Furthermore, the "median diameter measured by a laser diffraction / scattering method" refers to a particle diameter (D50) at which the cumulative weight is 50% in a particle size distribution obtained by a laser diffraction type particle size distribution measuring device and by a laser diffraction / scattering method.

[0234] In addition, the above numerical values ​​are not strictly speaking values, and there are errors for each product. If errors caused by measurement, etc. are included, it does not deny that an error of less than about 10% is mixed. From the perspective of this error, it is normally distributed. Since the particle size is normally distributed, even if it is considered that the median diameter ≈ the average particle diameter, the difference between the two is within a few percent and is considered to be an error.

[0235] -Content of manganese oxide catalyst and activated carbon-

[0236] The mixing ratio of the manganese oxide catalyst and the activated carbon is preferably 20 / 80≤activated carbon / manganese oxide catalyst≤80 / 20, and more preferably 30 / 70≤activated carbon / manganese oxide catalyst≤70 / 30 in terms of mass ratio.

[0237] When the mixing ratio of the manganese oxide-based catalyst and the activated carbon is within the above range, a synergistic effect of ozone decomposition by the combination of the manganese oxide-based catalyst and the activated carbon is particularly obtained, and thus higher ozone decomposition performance can be obtained.

[0238] The total amount of the manganese oxide catalyst and the activated carbon is preferably 60% to 90% by mass, more preferably 65% ​​to 85% by mass, and further preferably 70% to 80% by mass relative to the coating film.

[0239] When the total amount of the manganese oxide catalyst and the activated carbon is within the above range, high ozone decomposition performance can be obtained without impairing the adhesion of the coating film.

[0240] (Polyacrylate dispersant)

[0241] The polyacrylate-based dispersant is a dispersant that can achieve high dispersion of the manganese oxide-based catalyst and activated carbon.

[0242] The polyacrylate dispersant is, for example, a dispersant based on a polyacrylate salt, an acrylic acid skeleton or a modified acrylic acid skeleton. In addition, the polyacrylate dispersant also includes a modified polyacrylate dispersant.

[0243] The weight average molecular weight of the polyacrylate dispersant is preferably 5,000 to 30,000.

[0244] The higher the molecular weight of the polyacrylate dispersant, the more adsorption sites it has in the molecule. Therefore, even if the concentration of the dispersant is low, the manganese oxide catalyst and activated carbon can be adsorbed at many locations to prevent aggregation.

[0245] When the weight average molecular weight of the polyacrylate dispersant is 5000 or more, since the molecule has a sufficient number of adsorption sites, the adsorption sites increase, and the dispersibility of the manganese oxide catalyst and the activated carbon is further improved, thereby further improving the ozone decomposition performance of the coating film.

[0246] On the other hand, when the weight average molecular weight of the polyacrylate dispersant is 30,000 or less, the compatibility and affinity between the dispersant and the coating composition components can be suppressed, thereby preventing the reduction in the dispersibility of the manganese oxide catalyst and the activated carbon. Thus, the reduction in the ozone decomposition performance of the coating film can be suppressed.

[0247] Therefore, when a polyacrylate dispersant with a weight average molecular weight in the range of 5,000 to 30,000 is used, the compatibility with other materials is also good, thereby further improving the dispersibility of the manganese oxide catalyst and the activated carbon.

[0248] The weight average molecular weight of the polyacrylate dispersant is more preferably 6,000 to 28,000, and further preferably 7,000 to 25,000.

[0249] The weight average molecular weight (Mw) is a value obtained by measuring by gel permeation chromatography (GPC) and converting the chromatogram measured by GPC into a molecular weight of standard polystyrene.

[0250] The acid value of the polyacrylate dispersant is preferably 1 to 50. This is because it is possible to suppress deterioration in the adsorption of the dispersant which may occur due to the polarity of other materials such as additives such as pigments.

[0251] Therefore, if a dispersant having an acid value in the range of 1 to 50 is used, the dispersion stability of the catalyst and the activated carbon can be ensured without affecting the type of additives.

[0252] The acid value of the polyacrylate dispersant is more preferably 3-48, and even more preferably 5-45.

[0253] The acid value of the polyacrylate dispersant is a value measured by a neutralization titration method in accordance with JIS K0070.

[0254] The hydrogen ion index of the polyacrylate dispersant is preferably pH 4 to pH 9. For example, this is because it is possible to suppress the deterioration of the dispersibility of the additives that may occur due to the type of additives such as pigments. Therefore, if a dispersant with a hydrogen ion index in the range of pH 4 to pH 9 is used, it will not affect the type of additives, and the dispersion stability of the additives can be ensured.

[0255] The hydrogen ion index of the polyacrylate dispersant is more preferably pH 4.5 to pH 8.5, and further preferably pH 5 to pH 8.

[0256] The hydrogen ion index of the polyacrylate dispersant is a value measured at a liquid temperature of 25° C. for a resin dilution liquid (emulsion, dispersion, aqueous solution, etc.) having a resin concentration of approximately 1% to 99%.

[0257] Thus, when a polyacrylate dispersant having a weight average molecular weight in the range of 5000 to 30000, an acid value in the range of 1 to 50, and a hydrogen ion index in the range of pH 4 to pH 9 is used, a high ozone decomposition performance can be obtained without impairing the adhesion of the coating film. In addition, the dispersibility of the components of the coating composition is also improved.

[0258] Examples of commercially available polyacrylate dispersants include DESPERBYK from BYK-Chemie, EFKA from Ciba Specialty Chemicals or EFKA ADDITIVES BV (EFKA ADDITIVES), DISPARLON from Kusumoto Chemicals Co., Ltd., and SNTHICKENER (trade name) from SANNOPKO.

[0259] The content of the polyacrylate dispersant is preferably 1.5 to 75 parts by mass, more preferably 2 to 60 parts by mass, and even more preferably 2.5 to 50 parts by mass, based on 100 parts by mass of the total amount of the manganese oxide catalyst and the activated carbon.

[0260] When the content of the polyacrylate dispersant is within the above range, a high ozone decomposition property can be imparted to the coating film. In addition, both high ozone decomposition property of the coating film and high storage stability of the coating composition can be achieved simultaneously.

[0261] (resin)

[0262] The resin is a resin that binds the manganese oxide catalyst and the activated carbon in the coating film. The resin is preferably a water-based resin. The water-based resin may be any one of a water-soluble resin that can be dissolved in water and a water-dispersible resin that can be dispersed in water.

[0263] Examples of the resin include epoxy resins, epoxy ester resins, polyester resins, (meth) acrylic resins (i.e., acrylic resins and methacrylic resins), acrylic silicone resins, polyester resins, polyurethane resins, alkyd resins, polyurethane resins, vinyl resins, urea-formaldehyde resins, styrene-butadiene-latex (SBR), acrylonitrile-butadiene rubber (NBR), etc. The resins may be used alone or in combination of two or more.

[0264] Here, the resin may be added to the coating composition in the form of any one of a water-soluble resin (or a water-soluble resin aqueous solution), an emulsion resin, and a dispersion resin. In addition, "emulsion (also known as エマルション (Japanese name))" is also called an emulsion, and although the original meaning is that liquid particles in a liquid are colloidal particles or particles coarser than colloidal particles and are in an emulsion state (i.e., dispersed type) ("Iwanami Physical and Chemical Dictionary (Fifth Edition)" compiled by Saburo Nagakura and others, page 152, published by Iwanami Shoten Co., Ltd. on February 20, 1998), in this specification, the term "emulsion" is used as "a substance in which solid or liquid particles are dispersed in a liquid" in a generally used sense in a broader sense.

[0265] As the resin, in particular, from the perspective of compatibility and dispersibility of manganese oxide catalysts and activated carbon, weather resistance of the coating, cost, adhesion of the coating, and dispersion stability of each component, (meth) acrylic resin or polyacrylic resin is preferred. (Meth) acrylic resin has excellent adhesion to metals, and polyacrylic resin has excellent adhesion to metals and resins.

[0266] Therefore, the coating film containing (meth) acrylic resin has high adhesion to metal parts (ventilation parts, rotary blades, guide parts, etc.). In addition, the coating film containing polyacrylic resin has high adhesion to metal or resin parts (ventilation parts, rotary blades, guide parts, etc.).

[0267] The (meth)acrylic resin broadly includes acrylic resin and methacrylic resin.

[0268] The acrylic resin refers to a homopolymer or copolymer of a (meth)acrylic acid monomer selected from (meth)acrylic acid (referring to acrylic acid or methacrylic acid. The same applies hereinafter) and (meth)acrylate (referring to acrylic acid ester or methacrylate. The same applies hereinafter), or a copolymer of a (meth)acrylic acid monomer and a monomer copolymerizable with the (meth)acrylic acid monomer.

[0269] Examples of the (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, ethylhexyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 2,2-bis(hydroxymethyl)ethyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, glycidyl (meth)acrylate, aminoethyl (meth)acrylate, aminopropyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methoxyethyl (meth)acrylate, methoxypropyl (meth)acrylate, methoxybutyl (meth)acrylate, and stearyl (meth)acrylate.

[0270] As the monomer that can be copolymerized with (meth) acrylic monomer, it is preferably a monomer with an ethylene unsaturated group, for example, ethylene, propylene, butylene, butadiene, styrene, α-methylstyrene, vinylphenol, vinyl chloride, vinylidene chloride, vinyl acetate, vinyl chloride, vinyl benzoate, vinyl alcohol, allyl alcohol, crotonic acid, itaconic acid, maleic acid, fumaric acid, (meth) acrylamide, N-hydroxymethyl acrylamide, N-butoxymethylol (meth) acrylamide, (meth) acrylonitrile, etc. are listed. In addition, although as a copolymerization method, it is usually emulsion polymerization, it is not limited to this. In addition, in the case of acid, it can also be its alkali metal salt, alkaline earth metal salt, etc.

[0271] The (meth)acrylic resin may be modified with a urethane resin, an epoxy resin, a phenolic resin, a melamine resin, or the like, such as a urethane-modified (meth)acrylic resin, an epoxy-modified (meth)acrylic resin, a phenolic-modified (meth)acrylic resin, or a melamine-modified (meth)acrylic resin.

[0272] The (meth)acrylic resin is preferably a weakly basic (meth)acrylic resin having a hydrogen ion index in the range of pH 7 to pH 9. Since the weakly basic (meth)acrylic resin has high dispersibility in water as a solvent of the coating composition, it forms a dense coating film with good film-forming properties and uniformity, and also improves adhesion to the metal substrate.

[0273] The hydrogen ion index of a (meth)acrylic resin is a value measured at a liquid temperature of 25° C. for a resin dilution liquid (emulsion, dispersion, aqueous solution, etc.) having a resin concentration of about 1% to 99%.

[0274] In addition, the (meth)acrylic resin added to the coating composition is preferably a resin having a median diameter (average particle diameter) in the range of 50 nm to 150 nm. If it is in this range, the dispersibility of the resin component in water is high, the film-forming property and uniformity of the coating film are good, and the adhesion of the coating film to the metal substrate can be exerted.

[0275] The median diameter (average particle diameter) of the (meth)acrylic resin is more preferably 60 nm to 140 nm, and further preferably 70 nm to 130 nm.

[0276] On the other hand, polyacrylic acid resins include homopolymers obtained by polymerizing only propylene, random polymers obtained by copolymerizing a small amount of ethylene, and block copolymers obtained by dispersing a rubber component (EPR) in a homopolymer or a random polymer. In addition, polyacrylic acid resins also include modified polyacrylic acid resins and chlorinated polyacrylic acid resins.

[0277] The polyacrylic acid resin is preferably a weakly basic polyacrylic acid resin having a hydrogen ion index in the range of pH 7 to pH 9. Since the weakly basic polyacrylic acid resin has high dispersibility in water as a solvent of the coating composition, it forms a dense coating film with good film-forming properties and uniformity, and also improves adhesion to the metal substrate.

[0278] The hydrogen ion index of the polyacrylic acid resin is a value measured at a liquid temperature of 25° C. for a resin dilution liquid (emulsion, dispersion, aqueous solution, etc.) having a resin concentration of about 1% to 99%.

[0279] In addition, the weakly basic polyacrylic acid resin added to the coating composition preferably has a median diameter (average particle diameter) in the range of 50 nm to 150 nm. If it is within this range, the dispersibility of the resin component in water is high, the film-forming property and uniformity of the coating film are good, and the adhesion of the coating film to the metal substrate can be exerted.

[0280] The median diameter (average particle diameter) of the weakly basic polyacrylic acid resin is more preferably 60 nm to 140 nm, and further preferably 70 nm to 130 nm.

[0281] For example, the content of the resin is preferably in the range of 5 to 100 parts by mass, more preferably in the range of 10 to 50 parts by mass, relative to 100 parts by mass of the total blending amount of the manganese oxide catalyst and activated carbon (total blending amount of the solid content).

[0282] When the content of the resin is 5 parts by mass or more, good adhesion to the substrate is easily obtained, and peeling and missing of the coating film, and shedding of the manganese oxide-based catalyst and activated carbon can be further suppressed.

[0283] On the other hand, when the content of the resin is 100 parts by mass or less, a decrease in the ozone decomposition performance of the coating film can be further suppressed.

[0284] Therefore, the content of the above resin is preferred because it is easy to achieve both the adhesion of the coating film and the ozone decomposition property.

[0285] (pH adjuster)

[0286] The pH adjuster suppresses the precipitation of the manganese oxide catalyst and the activated carbon due to the decrease in the viscosity of the coating composition by neutralization, thereby making it easier to maintain high dispersibility of the manganese oxide catalyst and the activated carbon in the coating composition.

[0287] The pH adjuster is a compound that adjusts the hydrogen ion index of the coating composition for forming a coating film to a range of pH 7 to pH 12, more preferably pH 8 to pH 11.5, and even more preferably pH 9.5 to pH 11. The pH adjuster is a compound that also includes a neutralizer.

[0288] Examples of the pH adjuster include low-boiling-point amines such as triethylamine (TEA), ammonia water, and dimethylaminoethanol.

[0289] (Other ingredients)

[0290] The coating film may contain various additives other than the above-mentioned components.

[0291] For example, the coating film may also contain pigments such as coloring pigments, rust-proof pigments, extender pigments, functional pigments, etc. for improving rust resistance and chipping resistance, etc. In addition, the coating film may also include additives for improving the coating properties of the coating composition used to form the coating film and the coating film performance.

[0292] Examples of the coloring pigment include carbon black, titanium oxide, iron oxide, zinc oxide, organic azo chelate pigments, insoluble azo pigments, condensed azo pigments, diketopyrrolopyrrole pigments, benzimidazolone pigments, phthalocyanine pigments, indigo pigments, naphthoxylum pigments, perylene pigments, dioxane pigments, quinacridone pigments, isoindolinone pigments, metal complex pigments, chrome yellow, yellow iron oxide, red iron oxide, titanium dioxide, and the like.

[0293] Examples of the rust-proof pigment include zinc phosphate, zinc phosphite, aluminum polyphosphate, aluminum tripolyphosphate, zinc calcium molybdate, zinc orthoate, zinc polyphosphate, zinc molybdate, zinc phosphomolybdate, aluminum phosphomolybdate, zinc oxide, zinc phospho / silicate, zinc aluminum phosphate, calcium zinc phosphate, calcium zinc cyanamide, barium metaborate, and magnesium aminophosphate.

[0294] As the rust-proof pigment, from the viewpoint of environmental protection, a rust-proof pigment containing no harmful heavy metals such as a chrome-based rust-proof pigment is preferred.

[0295] The content of the rust-proof pigment is preferably 30% by mass or less, and more preferably 20% by mass or less, relative to the coating film. If the content of the rust-proof pigment is within the above range, the stability of the coating composition is also good.

[0296] Examples of the extender pigment include talc, calcium carbonate, barium sulfate, calcium sulfate, mica, clay, silica, diatomaceous earth, alumina, barium oxide, and silica.

[0297] In particular, talc is preferred as an extender pigment. Talc forms a multi-layer stack in the coating film, and the denseness of the layers formed by the arrangement of talc can prevent corrosion factors from invading the coating film.

[0298] As other additives, for example, viscosity modifiers, film-forming aids, dispersants mainly for dispersing pigments, defoamers, fillers, plasticizers, anti-sagging agents, film-forming aids, thixotropic agents, leveling agents, pH adjusters, neutralizers, ultraviolet absorbers, ultraviolet stabilizers, anti-settling agents, thickeners, curing catalysts, neutralizers, desiccants (i.e., drying agents), stabilizers, surface conditioners (i.e., coating surface conditioners), etc. are listed.

[0299] For example, as a dispersant that mainly disperses the pigment more satisfactorily, a polyvalent carboxylic acid-based dispersant or the like is cited.

[0300] As defoamers, for example, silicon defoamers, acrylic defoamers, etc. are cited. These defoamers can prevent the coating composition from becoming uneven due to the generation of fine bubbles when the coating composition is mixed, and adjust the viscosity and fluidity. In addition, by defoaming, bubbles are suppressed in the coating film. Thus, rust caused by moisture intruding from bubbles can be prevented, and the rust resistance of the coating film can be improved.

[0301] Examples of the desiccant include metal desiccants such as cobalt naphthenate and lead naphthenate. The desiccant can accelerate drying when the coating composition is applied to form a coating film, and can also accelerate further polymerization of the aqueous resin to form a dense coating film.

[0302] Examples of stabilizers include alkanolamine derivatives (diisopropanolamine, ethanolamine, diethanolamine, triisopropanolamine, triethanolamine, etc.). Stabilizers adjust fluidity, viscosity, dispersibility, etc., thereby stabilizing the coating composition. In addition, alkanolamine derivatives may also function as primary rust inhibitors.

[0303] (Method for producing coating composition for forming coating film)

[0304] Although one example of the method for producing the coating composition is described, the present invention is not limited thereto.

[0305] In the method for producing the coating composition, for example, first, a dispersing step is performed in which a solvent mainly composed of water, a manganese oxide catalyst, activated carbon, and a polyacrylate dispersant are mixed and the mixture is stirred by a disperser to disperse the catalyst and activated carbon.

[0306] Here, the solvent containing water as a main component is a solvent containing water at 50% by mass or more, 75% by mass or more, 90% by mass or more, 95% by mass or more, or 100% by mass relative to the total solvent.

[0307] Examples of the disperser used in the dispersion step include a ball mill, a bead mill, a high-pressure ejector, a dissolver, a Banbury mixer, a planetary mixer, a butterfly mixer, a screw mixer, a roller mill, a sand mill, a paint mixer, a grain grinder, a high-speed impeller mixer, an open kneader, a vacuum kneader, a grinder, a high-speed disperser, a homogenizer, a homogenizer, a colloid mill, a microfluidizer, an ultrasonic generator, and a cavity resonance type accelerator.

[0308] As the disperser, a bead mill or a roll mill is preferable. A bead mill or a roll mill can disperse the manganese oxide catalyst and activated carbon into a predetermined fine size with less energy.

[0309] Next, a neutralization step is performed in which the mixture that has undergone the dispersion step is mixed with a pH adjuster (ie, a neutralizer).

[0310] In the neutralization step, the pH adjuster is used to adjust the hydrogen ion index of the coating composition to preferably be in the range of pH 7 to pH 12, more preferably pH 8 to pH 11.5, and even more preferably pH 9.5 to pH 11. This is because the precipitation of the coating components due to the decrease in the viscosity of the coating composition can be prevented, and uniform dispersion and stabilization of the coating composition can be achieved, thereby making it easy to ensure uniform coating film performance after coating.

[0311] Next, a coating preparation step is performed in which the mixture that has undergone the neutralization step is mixed with a resin and stirred with a stirrer. In the coating preparation step, various additives are mixed with the resin into the mixture that has undergone the neutralization step as needed.

[0312] Through the above steps, the target coating composition can be obtained.

[0313] (Method for forming coating film)

[0314] The method for forming the coating film is not particularly limited, and a method of applying the coating composition to an object to be coated and then curing the coating composition is employed.

[0315] As the coating method, a known coating method can be adopted.

[0316] Examples of known coating methods include air spraying, showering, spraying, roll coating, curtain flow coating, die coating, brush coating, dip coating, extrusion (or extrusion), knife coater, rod coating, and electrostatic coating.

[0317] By a known coating method, the coating is applied to a predetermined coating portion on the coating object with an arbitrary coating amount, thickness, and coating pattern.

[0318] The film of the applied coating composition is naturally dried, heated dried, or forced dried using a dryer to remove the solvent and solidify the film, thereby forming a target coating film.

[0319] (Test example)

[0320] Here, the coating film having ozone decomposition performance and the aqueous coating composition forming the coating film will be described in more detail while showing test examples.

[0321] - Test Examples 1 to 3, Comparative Examples 1 to 6 -

[0322] First, Table 1 shows the blending compositions of test examples of water-based coating compositions for forming coating films.

[0323]

Table 1

[0324]

[0325] As shown in Table 1, the aqueous coating composition involved in Test Example 1 is composed of activated carbon (raw material: palm shell, average particle diameter: 5 μm, BET specific surface area: 2000 m 2 / g), manganese dioxide catalyst (manganese dioxide content: more than 70%, average particle diameter: 5μm, BET specific surface area: 250m 2 / g), a polyacrylate dispersant, water as a solvent, triethylamine (TEA) as a pH adjuster (neutralizer), an aqueous dispersion containing a polyacrylic acid resin as a resin, and additives (viscosity modifier, thickening aid).

[0326] The water-based coating compositions according to Test Examples 2 and 3 are examples in which an aqueous dispersion containing an acrylic resin is used instead of the polyacrylic resin of Test Example 1. The other materials are the same as those of Test Example 1.

[0327] In Table 1, activated carbon is expressed in terms of solid content, and water in the dispersion step is a value including the amount of water contained in the activated carbon material as a solvent in advance in addition to ion exchange water added as a solvent.

[0328] When the water-based coating compositions according to Test Examples 1 to 3 were prepared, first, a dispersing step was performed in which activated carbon, a manganese dioxide-based catalyst, water as a solvent, and a polyacrylate-based dispersant were mixed according to the blending in Table 1 and the mixture was dispersed in a bead mill.

[0329] The bead mill at this time used 1.5 mm zircon (zirconia bead mill) as a medium, and the mixed material was dispersed under the condition of a rotation speed of 1500 rpm×90 minutes.

[0330] Thus, in Test Examples 1 to 3, the maximum particle diameter (Dmax) of the particle size of the particles (activated carbon and manganese dioxide catalyst) in the dispersed mixture was made 20 μm or less by measuring with a linear method using a fineness meter according to JIS K 5600 and JIS K 5400 (1990). In addition, the cumulative particle diameter (D90) of 90% of the volume basis was made 10 μm or less by measuring with a laser analysis method using a laser diffraction particle size distribution measuring device.

[0331] Next, a neutralization step of adding triethylamine (TEA) as a pH adjuster to the obtained mixture according to the blending shown in Table 1 to neutralize the mixture was performed.

[0332] Next, the following coating process was implemented, that is, the neutralized mixture was mixed with a polyacrylic resin (solid content mass percentage 30%) or an acrylic resin (solid content mass percentage 40%) as a resin by blending according to Table 1, and then additives (viscosity modifier, thickening aid) were further mixed, and the mixture was stirred for 5 minutes to 10 minutes using a dispersant to mix and disperse the various materials.

[0333] Through the above steps, the water-based coating compositions according to Test Examples 1 to 3 were obtained.

[0334] On the other hand, for comparison, water-based coating compositions according to Comparative Examples 1 to 6 were prepared using the blending combinations shown in Table 1 using a dispersant different from that in the test example or without using a dispersant.

[0335] Comparative Example 1 is an example in which no dispersant was used.

[0336] Comparative Example 2 is an example in which a polycarboxylic acid ammonium salt (negative ion) was used as a dispersant instead of the polyacrylate-based dispersant used in the test example.

[0337] Comparative Examples 3 and 6 are examples in which a polycarboxylic acid sodium salt (negative ion) was used as a dispersant instead of the polyacrylate-based dispersant used in the test examples.

[0338] Comparative Example 4 is an example in which a phosphoric acid ester was used as a dispersant instead of the polyacrylate-based dispersant used in the test example.

[0339] Comparative Example 5 is an example in which polyurethane was used as a dispersant instead of the polyacrylate-based dispersant used in the test example.

[0340] In addition, the aqueous coating compositions according to these comparative examples were also prepared by the same procedure as in the above-mentioned test examples.

[0341] Here, about various water-based coating compositions of the test examples and comparative examples prepared according to the blending in Table 1, the storage stability and ozone decomposition properties thereof were evaluated in a test.

[0342] Regarding storage stability, the prepared aqueous coating composition was stored at 20°C for one month, and the presence or absence of aggregation was confirmed after one month. A case where no aggregation occurred even after storage at 20°C for one month was designated as A, and a case where sedimentation separation occurred due to aggregation was designated as C.

[0343] Regarding ozone decomposition, use Figure 4 Specifically, the ozone decomposition test device 200 shown in FIG. Figure 4 In the tube 210 of the ozone decomposition test device 200 shown, a test body T coated with a coating composition and dried on a polypropylene TP substrate 220 (hereinafter referred to as PP material 220) is placed flat for evaluation. The test body T is a test body formed with a cured coating film 220A on the PP material 220 by coating the coating composition on the surface of the PP substrate 220 having a surface of 5 cm×7 cm with a coating area of ​​5 cm×7 cm and drying at 100°C×10 minutes.

[0344] In addition, the coating composition is applied to the PP material 220 until the base thereof is covered.

[0345] Then, air containing ozone (initial ozone concentration: 4.0 ppm (volume basis), temperature: 25° C.) was supplied and circulated into the tube 210 in which the test body T was placed at a wind speed of 1.0 m / s, and the ozone concentration before passing through the PP material 220 with the cured coating film 220A, that is, the test body T, was measured using the ozone sensor 231. In addition, the ozone concentration near the test body T was measured using the ozone sensor 232.

[0346] In addition, the distance x between the ozone sensor 232 and the cured coating film 220A was set to 2 mm. In addition, the evaluation test was performed at room temperature (normal temperature) of about 25°C.

[0347] Then, the ozone decomposition rate (={(b1-b2) / b1}×100)(%) obtained by curing the coating film 1 is calculated based on the ozone concentration b1 measured by the ozone sensor 231 and the ozone concentration b2 measured by the ozone sensor 232. The ozone decomposition removal rate at this time is set as A when it is 24% or more, B when it is 18% or more and less than 24%, and C when it is less than 18%.

[0348] As a comprehensive evaluation, the case where both the storage stability and ozone decomposition evaluation tests were A was recorded as A, and the other cases were recorded as C. The results of these evaluation tests are shown in the lower part of Table 1.

[0349] As shown in the lower part of Table 1, in the aqueous coating compositions of Test Examples 1 to 3 in which a polyacrylate dispersant was used as a dispersant, the manganese dioxide catalyst and the activated carbon were highly dispersed, and since the dispersion stability was also high, no aggregation occurred even when stored at 20°C for one month, and the storage stability was high.

[0350] In addition, the cured coating films formed from the aqueous coating compositions of Test Examples 1 to 3 had less granularity or roughness. In addition, the cured coating films had excellent film-forming properties that allowed the substrate to be sufficiently shielded with a thin film having a dry film thickness of about 5 μm, and also had relatively excellent ozone decomposition performance.

[0351] On the other hand, in Comparative Example 1 in which no dispersant was used, the activated carbon and the manganese dioxide-based catalyst were not dispersed but aggregated and gelled, and thus could not be prepared into a coating.

[0352] Even in Comparative Example 2 in which a polyvalent carboxylic acid ammonium salt was used as a dispersant, the activated carbon and the manganese dioxide-based catalyst were not dispersed but aggregated and gelled, and thus could not be formed into a coating.

[0353] On the other hand, in Comparative Examples 3 to 5, which use polycarboxylic acid sodium salt (negative ion), phosphate, and polyurethane as dispersants, although coating can be achieved, due to the low dispersibility and dispersion stability of activated carbon and manganese dioxide catalysts, agglomeration occurs during storage at 20°C for one month, which causes problems in storage stability. In addition, the dispersibility of manganese dioxide catalysts and activated carbon is low, and they will not become finer particles as in the test examples using polyacrylate dispersants. As a result, more granularity and roughness of the coating will be produced after coating. In addition, in order to fully cover the substrate, the film thickness of the coating after coating is thicker, resulting in poor film-forming properties. Moreover, compared with the test examples using polyacrylate dispersants, the ozone decomposition performance is also poor.

[0354] In Comparative Example 6, although the storage stability can be improved by increasing the amount of polycarboxylic acid sodium salt (negative ion) as a dispersant, the ozone decomposition property is reduced. This is considered to be because the amount of the dispersant is large, and the ozone adsorbed on the activated carbon and the manganese dioxide catalyst is blocked by the dispersant. That is, in Comparative Example 6, the storage stability cannot be ensured with a small amount of the dispersant, and on the other hand, when the amount of the dispersant is increased, the adsorption of ozone on the activated carbon and the manganese dioxide catalyst is blocked by the dispersant, so the desired ozone decomposition property cannot be obtained compared with the test example.

[0355] Thus, in the dispersants used in the respective comparative examples, it was not possible to simultaneously achieve good storage stability and ozone decomposition properties.

[0356] In contrast, in Test Examples 1 to 3 using a polyacrylate dispersant, the activated carbon and the manganese dioxide catalyst can be finely dispersed with a small amount of dispersant. In addition, in Test Examples 1 to 3, since reagglomeration is less, and the dispersion degree and dispersion stability are excellent, the storage stability is good, and the granularity and roughness of the cured coating are less, so the film-forming property and appearance are good, and excellent ozone decomposition performance is exerted.

[0357] That is, in this test example, the polyacrylate dispersant can finely disperse the activated carbon and manganese dioxide catalyst even with the relatively small amount used, thereby increasing the amount of ozone that can be adsorbed on the activated carbon and manganese dioxide catalyst. As a result, the ozone decomposition performance of the activated carbon and manganese dioxide catalyst can be exerted without waste, resulting in excellent ozone decomposition performance. In addition, the dispersion stability is also high, and the storage stability is excellent. Therefore, long-term stable storage can be implemented, and long-term storage performance is improved.

[0358] In Comparative Examples 3 to 5, as described above, the activated carbon and manganese dioxide catalysts had low dispersibility and thus agglomerated a lot. As a result, the formed cured coatings had a lot of graininess and roughness, and the film-forming properties and adhesion to the substrate of the coatings were low, resulting in poor coating appearance.

[0359] In contrast, in the present test example, the activated carbon and the manganese dioxide catalyst were finely dispersed by using the polyacrylate dispersant, so that the formed cured coating film had less granularity and roughness and had good film-forming properties and appearance.

[0360] In addition, in Test Examples 1 to 3 in which polyacrylic resin and acrylic resin were used as resins, even when the adhesion test described later was carried out on a metal substrate, the number of peeled squares was less than two, thereby achieving high adhesion and bonding properties even on a metal substrate.

[0361] In particular, in Test Examples 2 and 3 in which polyacrylic resin was used as the resin, not only for metal substrates but also for resin substrates, the number of peeled squares was reduced to less than two through the adhesion test described later, thereby achieving higher adhesion and bonding properties even for resin substrates.

[0362] Therefore, when polyacrylic acid resin is used as the resin, high adhesion of the coating film can be ensured for metal and resin substrates. Furthermore, since no special processing equipment is required for the adhesion of the coating film, cost reduction can be achieved.

[0363] On the other hand, when acrylic resin is used as the resin, the adhesiveness and adhesion to the metal substrate are good. However, in order to ensure high adhesion of the coating film to the resin substrate, it is preferable to apply the coating after pre-treating the substrate.

[0364] -Test Examples 2-1 to 2-8-

[0365] As shown in Table 2, the present inventors conducted a detailed study on the optimal blending amount of the polyacrylate dispersant.

[0366] That is, only the blending amount (g) of the polyacrylate dispersant in the blending combination of Test Example 2 shown in Table 1 was changed, and all the blending materials other than the polyacrylate dispersant were unified to be the same as in Test Example 2, thereby preparing various aqueous coating compositions with different concentrations of the polyacrylate dispersant.

[0367] Here, the same materials as those in Table 1 were used and the same procedures were followed to produce the samples.

[0368] Furthermore, the storage stability test evaluation and the ozone decomposition test evaluation were carried out in the same manner as in Table 1 above with respect to the aqueous coating composition in which the concentration of the polyacrylate dispersant was varied.

[0369]

Table 2

[0370]

[0371] As shown in Table 2, Test Example 2-1 is an example in which the polyacrylate dispersant is contained in the aqueous coating composition at a concentration of 0.1% by mass, so that the amount of the polyacrylate dispersant blended is 0.9 parts by mass relative to 100 parts by mass of the total amount of the manganese dioxide catalyst and the activated carbon (total amount of the solid content). In this example, compared with Test Examples 2-2 to 2-7, the dispersion stability of the activated carbon and the manganese dioxide catalyst was poor, and agglomeration occurred during storage at 20°C for one month.

[0372] On the other hand, Test Example 2-8 is an example in which the polyacrylate dispersant is contained in the aqueous coating composition at a concentration of 9.1 mass %, so that the amount of the polyacrylate dispersant blended is 86.2 mass parts relative to 100 mass parts of the total amount of the manganese dioxide catalyst and the activated carbon (total amount of the solid content). In this example, the ozone decomposition rate is lower than that of Test Examples 2-2 to 2-7.

[0373] This is considered to be because the amount of the dispersant was large, and thus ozone that was intended to be adsorbed on the activated carbon and the manganese dioxide-based catalyst was blocked by the dispersant.

[0374] In contrast, Test Examples 2-2 to 2-7 are examples in which the polyacrylate dispersant is contained in the aqueous coating composition at a concentration of 0.3 to 4.8% by mass, so that the amount of the polyacrylate dispersant is within the range of 2.6 to 43.1 parts by mass relative to 100 parts by mass of the total amount of the manganese dioxide catalyst and the activated carbon (total amount of the solid content). In this example, it was confirmed that the manganese dioxide catalyst and the activated carbon were highly dispersed by the appropriate amount of the polyacrylate dispersant, and the dispersion stability was also good, and high storage stability and ozone decomposition were achieved at the same time without hindering the adsorption of ozone.

[0375] In addition, the present inventors have confirmed that if the amount of the polyacrylate dispersant blended is preferably 1.5 parts by mass or more, more preferably 2 parts by mass or more, and further preferably 2.5 parts by mass or more, relative to 100 parts by mass of the total amount of the manganese dioxide catalyst and the activated carbon (total amount of the solid content), storage stability can be particularly ensured. In addition, it has been confirmed that if the amount of the polyacrylate dispersant blended is preferably 75 parts by mass or less, more preferably 60 parts by mass or less, and further preferably 50 parts by mass or less, particularly high ozone decomposition properties are obtained, and the film-forming properties, adhesion properties, and appearance of the coating film are also good.

[0376] Therefore, relative to the total amount of manganese dioxide catalyst and activated carbon (total amount of solid components) 100 parts by mass, the polyacrylate dispersant is preferably blended in the range of 1.5 parts by mass to 75 parts by mass. If within this range, it is possible to effectively achieve high storage stability and ozone decomposition at the same time, and the film-forming property, adhesion and appearance of the coating are also good. Relative to the total amount of manganese dioxide catalyst and activated carbon (total amount of solid components) 100 parts by mass, the blending amount of the polyacrylate dispersant is more preferably in the range of 2 parts by mass to 60 parts by mass, and further preferably in the range of 2.5 parts by mass to 50 parts by mass.

[0377] In the water-based coating composition, the concentration of the polyacrylate dispersant is preferably in the range of 0.3 to 5% by mass. Within this range, high storage stability and ozone decomposition can be effectively achieved simultaneously, and the film-forming property, adhesion and appearance of the coating are also good. In the water-based coating composition, the concentration of the polyacrylate dispersant is more preferably 0.3 to 2% by mass.

[0378] - Test Examples 4 to 8, Comparative Examples 7 to 8 -

[0379] As shown in the following Tables 3 and 4, the present inventors conducted detailed studies on the optimal blending of the manganese dioxide-based catalyst and activated carbon.

[0380] First, the influence of the blending ratio (ratio) of activated carbon and manganese dioxide catalyst with ozone decomposition performance on water-based coating composition and the coating performance formed therefrom was investigated. Specifically, as shown in Table 3 below, various coating compositions were produced by changing the blending ratio (ratio) of activated carbon and manganese dioxide. Here, the same materials as in Table 1 were used, and produced according to the same steps. In addition, the coating composition produced was subjected to the test of storage stability and ozone decomposition.

[0381] Here, regarding the storage stability test of the water-based coating composition, the presence or absence of coagulation after storage at a temperature of 20° C. for one month was confirmed and evaluated in the same manner as in Table 1. In addition, although the sedimentation separation caused by coagulation after storage at 20° C. for one month was rare, the case where there was no problem with the coating property by stirring during coating was recorded as B.

[0382] On the other hand, the ozone decomposition test was carried out in the following manner. Figure 5 As shown, a test body T coated with an aqueous coating composition and dried on a polypropylene TP substrate 220 (PP material 220) is placed in a 20L polyester film bag 250 for evaluation. The test body T is a test body in which a cured coating film 220A is formed on the PP material 220 by coating the coating composition on the surface of the PP substrate 220 having a surface of 5cm×7cm with a coating area of ​​5cm×7cm and drying at 100°C×10 minutes.

[0383] Next, after air was sealed in the polyester film bag 250 by blowing, ozone generated by an ozone generator was injected, and after the ozone concentration in the bag 250 was adjusted to 0.2 ppm (volume basis), the polyester film bag 250 was sealed by heat sealing. Then, after 30 minutes, the ozone concentration in the polyester film bag 250 was measured by the ozone sensor 233, and the ozone decomposition rate was calculated by comparison with the initial ozone concentration.

[0384] The evaluation test in this case was performed at room temperature (normal temperature) of 25° C. In addition, various coating compositions were applied to the PP material 220 until the base was covered.

[0385] Furthermore, for comparison, Comparative Examples 7 and 8 were prepared in which only one of the activated carbon or the manganese dioxide-based catalyst was blended. The storage stability and ozone decomposition performance evaluation tests were also carried out in the same manner for these examples.

[0386] The upper part of Table 3 shows the blending combinations of various coating compositions produced, and the lower part of Table 3 shows the results of the evaluation test. In Table 3, the activated carbon is expressed as a solid content conversion amount, and the water in the dispersion step is a value including the amount of water as a solvent previously contained in the product of the activated carbon material in addition to the ion exchange water added as a solvent.

[0387]

Table 3

[0388]

[0389] As shown in Table 3, in Comparative Example 7 in which activated carbon was not blended but only a manganese dioxide-based catalyst was blended, the ozone decomposition rate was 75.9%, which was lower than that of the test example.

[0390] In addition, in Comparative Example 8 in which no manganese dioxide catalyst was added but only activated carbon was added, the ozone decomposition rate was also 50%, which was much lower than that of the test example. Furthermore, the storage stability was also extremely low.

[0391] This is because activated carbon aggregates by adsorbing a large amount of resin components (ie, organic matter) as coating film components due to its adsorption characteristics. It is known that when only activated carbon is blended, coating stability, ie, storage stability, cannot be ensured.

[0392] In contrast, in the test examples using a manganese dioxide catalyst and activated carbon together, the ozone decomposition rate was significantly improved compared to Comparative Examples 7 and 8 using only a manganese dioxide catalyst or only activated carbon alone, and extremely high ozone decomposition performance was shown.

[0393] Here, when the amount of manganese dioxide catalyst and activated carbon in the activated carbon required to ensure the predetermined high ozone decomposition performance increases, it is sometimes difficult to ensure the stability of the coating (i.e., storage stability). In addition, since the activated carbon is oxidized and consumed and deteriorated by long-term use, it is sometimes difficult to ensure high durability.

[0394] On the other hand, sometimes, even if the blending ratio of activated carbon is small, the ozone purification effect achieved by the activated carbon will not be produced, so the improvement effect of the ozone decomposition performance achieved by the combination of activated carbon and manganese dioxide catalyst is small, and it is difficult to obtain high ozone decomposition performance.

[0395] In particular, manganese dioxide catalysts are susceptible to moisture, chlorides, and atmospheric SO x and MO x , and thus the ozone decomposition property is likely to be reduced. Therefore, in order to ensure high ozone decomposition property for a long time, it is preferable to set the blending ratio to a predetermined amount relative to the activated carbon.

[0396] According to the dedicated experimental research of the inventors, as Test Examples 4 to 8, as shown in Table 3, by preferably setting the ratio of activated carbon and manganese dioxide catalyst in the aqueous coating composition to 20 / 80≤activated carbon / manganese dioxide catalyst≤80 / 20, a good ozone decomposition rate can be obtained, and practical storage stability can be easily ensured.

[0397] In particular, as shown in Test Examples 5 to 7, by more preferably setting the ratio of activated carbon to manganese dioxide-based catalyst (mass ratio of solid components) to 30 / 70≤activated carbon / manganese dioxide-based catalyst≤70 / 30, excellent ozone decomposition rate and storage stability are obtained, and it is easy to ensure extremely high ozone decomposition performance and coating stability for a long time.

[0398] In addition, the ratio of activated carbon to manganese dioxide catalyst in the aqueous coating composition (mass ratio of solid content) is consistent with the ratio of activated carbon to manganese dioxide catalyst in the coating film component formed by the aqueous coating composition. That is, when the ratio of activated carbon to manganese dioxide catalyst in the aqueous coating composition is 20 / 80≤activated carbon / manganese dioxide catalyst≤80 / 20, even in the cured coating film obtained from the aqueous coating composition, activated carbon and manganese dioxide catalyst are contained in a ratio of 20 / 80≤activated carbon / manganese dioxide catalyst≤80 / 20.

[0399] -Test Examples 7-1 to 7-5-

[0400] In addition, in order to investigate the amount of activated carbon and manganese dioxide catalysts with ozone decomposition performance and their effects on coating performance, the inventors conducted the following test. The test conducted was to increase or decrease the amount of activated carbon and manganese dioxide catalysts when the blending ratio (mass ratio of solid components) of the activated carbon and manganese dioxide catalysts in the blending combination of Test Example 7 shown in Table 3 was fixed at activated carbon / manganese dioxide catalyst = 70 / 30. Specifically, as shown in Table 4, various coating compositions were prepared by blending activated carbon and manganese dioxide catalysts in a coating formed by an aqueous coating composition so that the concentration of activated carbon and manganese dioxide catalysts was 33% to 83% by mass.

[0401] The blending combination and materials other than the activated carbon and the manganese dioxide catalyst were all the same as those in Test Example 7, and the preparation was carried out according to the same steps as above. That is, the blending amounts (g) of the blending materials other than the activated carbon and the manganese dioxide catalyst were all the same as those in Test Example 7, and only the blending amounts (g) of the activated carbon and the manganese dioxide catalyst were changed, and the preparation was carried out according to the same steps as above.

[0402] Furthermore, the prepared coating composition was tested for ozone decomposition properties and adhesion to a substrate.

[0403] Here, the same method as in the above-mentioned Test Example 1 was used. Figure 4 The ozone decomposition test apparatus shown was used to carry out the ozone decomposition test.

[0404] For the adhesion test, a sample was used in which a cured coating film was formed on a PP substrate by air spraying the aqueous coating composition on the PP substrate and drying the composition at 100° C. for 10 minutes.

[0405] In addition, regarding the sample, the adhesion (adhesion achieved by the cross-cutting method) was evaluated in accordance with JIS-K5600-5-6:1999. Specifically, 11 parallel cuts were made on the cured coating film of the sample at intervals of 1 mm in the longitudinal and transverse directions using a cutter to form a total of 100 1 mm×1 mm squares. Next, a tape (i.e., masking tape) was firmly crimped and pasted on the portion forming the 100 squares, and then peeled off all at once, and the number of peeled squares out of the 100 squares was measured. If the number of peeled squares is two or less, it is recorded as A, and if more than three peelings are observed, it is recorded as B.

[0406] The upper part of Table 4 shows the concentrations of activated carbon and manganese dioxide-based catalysts in the various coating compositions prepared, and the lower part of Table 4 shows the results of the evaluation tests.

[0407]

Table 4

[0408]

[0409] As shown in Table 4, it can be seen that the higher the concentration of activated carbon and the manganese dioxide-based catalyst, the higher the ozone decomposition performance.

[0410] In particular, as shown in Test Examples 7-3 to 7-5, when the concentration of the activated carbon and the manganese dioxide-based catalyst in the coating film formed from the aqueous coating composition was 63% or more, high ozone decomposition performance was obtained.

[0411] Furthermore, as shown in Test Examples 7-4 and 7-5, when the catalyst concentration in the coating component is 73% or more, even if the catalyst concentration is increased, the dispersibility is limited at a predetermined amount of dispersant, and therefore it is estimated that the improvement in ozone decomposition performance is small.

[0412] On the other hand, as shown in Test Example 7-5, when the concentration of activated carbon and manganese dioxide catalyst becomes too high, the adhesion performance is reduced. When the adhesion performance to the substrate is low, the coating film may be easily peeled off and the coating film components may fall off, so that it is impossible to obtain a continuously high ozone decomposition performance.

[0413] Here, according to the experimental research of the present inventors, it is confirmed that when the ratio of activated carbon and manganese dioxide catalyst in the aqueous coating composition (i.e., in the coating film) (mass ratio of solid content) is 20 / 80≤activated carbon / manganese dioxide catalyst≤80 / 20, when the total amount of activated carbon and manganese dioxide catalyst in the coating film component (total amount of solid content) is preferably 60% by mass or more, more preferably 70% by mass or more, a higher ozone decomposition performance can be obtained. In addition, it is confirmed that if the total amount of activated carbon and manganese dioxide catalyst in the coating film (total amount of solid content) is preferably 90% by mass or less, more preferably 85% by mass or less, the adhesion performance of the coating film to the substrate is also good.

[0414] Therefore, the total amount of activated carbon and manganese dioxide catalyst in the coating film (total amount of solid content) is preferably 60% to 90% by mass, and more preferably 70% to 80% by mass. This ensures adhesion to the substrate and maintains high ozone decomposition performance for a long time.

[0415] The total amount (mass %) of activated carbon and manganese dioxide in the coating film formed from the aqueous coating composition is a value calculated by: total solid content of activated carbon and manganese dioxide / solid content ratio of the entire aqueous coating composition as coating film components×100.

[0416] As described above, according to the above test examples, since the manganese dioxide catalyst and activated carbon can be finely and highly dispersed by the polyacrylate dispersant, it is difficult to produce a granular feeling on the cured coating film, and a coating film with high film-forming and adhesion properties can be formed. Moreover, a large amount of ozone can be attached by the highly dispersed manganese dioxide catalyst and activated carbon, so that a higher ozone decomposition performance can be exerted. In particular, by using a manganese dioxide catalyst whose catalytic activity of ozone decomposition is also high even in manganese oxide catalysts, a higher ozone decomposition performance is obtained. Moreover, by using the manganese dioxide catalyst and activated carbon together, a higher ozone decomposition performance is obtained compared with the case where they are used in the form of monomers. In addition, since activated carbon can be obtained at a low price, the cost can be suppressed. In addition, since the dispersion stability of the manganese dioxide catalyst activated carbon is also high by the polyacrylate dispersant, good coating stability and storage stability in practicality are obtained.

[0417] As the manganese dioxide catalyst, it is preferred to use a manganese dioxide catalyst having a median diameter (average particle diameter) in the range of 1 to 20 μm and a BET specific surface area in the range of 100 to 400 m 2According to the manganese dioxide-based catalyst having such characteristics, the dispersibility and dispersion stability of the coating composition are particularly high, and a coating film with high ozone decomposition performance is obtained.

[0418] As activated carbon, it is preferred to use one having a median diameter (average particle diameter) in the range of 1 to 20 μm and a BET specific surface area in the range of 500 to 3000 m 2 According to the activated carbon having such characteristics, the dispersibility and dispersion stability of the coating composition are particularly high, and a coating film with high ozone decomposition performance is obtained.

[0419] The polyacrylate dispersant is preferably one having a weight average molecular weight in the range of 500 to 30,000, an acid value in the range of 1 to 50, and a pH in the range of 5 to 9. The polyacrylate dispersant having such characteristics can achieve high dispersion and stable dispersion of the coating component with a relatively small amount of the dispersant without impairing the ozone decomposition performance.

[0420] The content of the polyacrylate dispersant is preferably in the range of 1.5 to 70 parts by mass relative to 100 parts by mass of the total amount of the manganese dioxide catalyst and the activated carbon. Thus, particularly high ozone decomposition and storage stability can be achieved simultaneously. In addition, by making the polyacrylate dispersant contained in the aqueous coating composition in the range of 0.3% to 5% by mass, particularly high ozone decomposition and storage stability can be achieved simultaneously.

[0421] Resin is preferably (meth) acrylic resin or polyacrylic resin. The compatibility of the manganese dioxide catalyst and activated carbon of these resins is also good, and the manganese dioxide catalyst and activated carbon are easily and evenly dispersed in the resin. Especially, according to (meth) acrylic resin, because the selection range of the molecular weight is large, therefore, it is easy to design the characteristics of the target coating performance, and then it is possible to form a coating with weather resistance, water resistance, and chemical resistance. In addition, according to polyacrylic resin, in addition to the metal substrate, the adhesion of the substrate made of resin is also excellent, so that the coating performances such as ozone decomposition performance can be well exerted for a long time.

[0422] Furthermore, it is preferred that the manganese dioxide catalyst and activated carbon are blended at a mass ratio (mass ratio of solid content) of 20 / 80≤activated carbon / manganese dioxide catalyst≤80 / 20. Thus, while ensuring the stability of the coating, a synergistic effect of ozone decomposition achieved by the combination of the manganese dioxide catalyst and activated carbon is obtained.

[0423] Preferably, the manganese oxide catalyst and activated carbon are blended together in such a manner that the total amount of the manganese oxide catalyst and activated carbon in the coating film is in the range of 60% to 90% by mass. This makes it possible to obtain high ozone decomposition performance without impairing the adhesion of the coating film to the substrate.

[0424] As described above, it is known that the ozone decomposing coating film including the manganese oxide-based catalyst, activated carbon, the polyacrylate-based dispersant, and the resin has high ozone decomposition performance.

[0425] Therefore, it can be seen that the blower having the ozone decomposing coating film can send out air with a reduced ozone concentration.

Claims

1. A blower comprising: A blower unit that sucks in and delivers air; An ozone-degradable coating film is provided at least one of a position contacted by the air delivered from the blast section and a position contacted by the air sucked into the blast section, wherein the ozone-degradable coating film is composed of a cured coating film of an aqueous coating composition, wherein the aqueous coating composition contains a manganese oxide catalyst, activated carbon, a polyacrylate dispersant, and a resin, and also contains a solvent mainly composed of water and a pH regulator. The resin is at least one selected from (meth) acrylic resin and polyacrylic resin, The manganese oxide catalyst is a manganese dioxide catalyst. The blending ratio of the manganese oxide catalyst to the activated carbon is 20 / 80≤activated carbon / manganese oxide catalyst≤50 / 50 in terms of mass ratio. The content of the polyacrylate dispersant is in the range of 2.6 parts by mass to 43.1 parts by mass relative to 100 parts by mass of the total amount of the manganese oxide catalyst and the activated carbon. The polyacrylate dispersant has a weight average molecular weight in the range of 5,000 to 30,000, an acid value in the range of 1 to 50, and a hydrogen ion index in the range of pH 4 to pH 9.

2. The blower according to claim 1, wherein: The invention comprises at least one of a first ventilation component and a second ventilation component, wherein the first ventilation component has a first ventilation hole for passing the air sent from the blowing section, and the ozone-degrading coating is provided on the wall surface of the first ventilation hole, and the second ventilation component has a second ventilation hole for passing the air sucked into the blowing section, and the ozone-degrading coating is provided on the wall surface of the second ventilation hole.

3. The blower according to claim 2, wherein: The first ventilation member is a honeycomb structure member having through holes as the first ventilation holes.

4. The blower according to claim 2 or claim 3, wherein: The second ventilation member is a honeycomb structure member having through holes as the second ventilation holes.

5. The blower according to claim 2, wherein: The first ventilation member is a filter member having mesh holes as the first ventilation holes.

6. The blower according to any one of claims 2, 3 or 5, wherein: The second ventilation member is a filter member having mesh holes as the second ventilation holes.

7. The blower according to claim 2 or claim 3, wherein: The air blowing unit includes a rotary blade having the ozone decomposing coating film provided on a blade surface.

8. The blower according to claim 2 or claim 3, wherein: A guide member is provided for guiding the air sent out from the blower toward the first ventilation member.

9. The blower according to any one of claims 1 to 3, wherein: The total amount of the manganese oxide catalyst and the activated carbon is 60% by mass to 90% by mass with respect to the ozone decomposing coating film.

10. An article with an ozone-degradable coating, comprising: The main body of the object; An ozone-degradable coating film is provided on the main body of the article, wherein the ozone-degradable coating film is composed of a cured coating film of an aqueous coating composition, wherein the aqueous coating composition contains a manganese oxide catalyst, activated carbon, a polyacrylate dispersant, and a resin, and also contains a solvent mainly composed of water and a pH regulator. The resin is at least one selected from (meth) acrylic resin and polyacrylic resin, The manganese oxide catalyst is a manganese dioxide catalyst, the blending ratio of the manganese oxide catalyst to the activated carbon is 20 / 80≤activated carbon / manganese oxide catalyst≤50 / 50 in terms of mass ratio, and the content of the polyacrylate dispersant is in the range of 2.6 to 43.1 parts by mass relative to 100 parts by mass of the total amount of the manganese oxide catalyst and the activated carbon, The polyacrylate dispersant has a weight average molecular weight in the range of 5,000 to 30,000, an acid value in the range of 1 to 50, and a hydrogen ion index in the range of pH 4 to pH 9.

11. The article with an ozone-degradable coating according to claim 10, wherein The main body of the article is a honeycomb structure component, a filter component, a pipe or a building material.

12. An air conditioning system, wherein: A device comprising at least one selected from the blower according to any one of claims 1 to 9 and the article with an ozone-degradable coating according to claim 10 or 11, and one or both of the blower and the article with an ozone-degradable coating.

13. An ozone decomposition method, wherein: An ozone-decomposing coating film is brought into contact with the atmosphere to decompose ozone in the atmosphere, wherein the ozone-decomposing coating film is composed of a cured coating film of an aqueous coating composition, wherein the aqueous coating composition contains a manganese oxide catalyst, activated carbon, a polyacrylate dispersant, and a resin, and further contains a solvent mainly composed of water and a pH adjuster, wherein the resin is at least one selected from a (meth)acrylic resin and a polyacrylic resin, and the manganese oxide catalyst is a manganese dioxide catalyst, and the blending ratio of the manganese oxide catalyst to the activated carbon is 20 / 80≤activated carbon / manganese oxide catalyst≤50 / 50 in terms of mass ratio, and the content of the polyacrylate dispersant is in the range of 2.6 to 43.1 parts by mass relative to 100 parts by mass of the total amount of the manganese oxide catalyst and the activated carbon, and the polyacrylate dispersant has a weight average molecular weight in the range of 5000 to 30000, an acid value in the range of 1 to 50, and a hydrogen ion index in the range of pH 4 to pH 9.

14. A method for forming an ozone decomposing film, wherein: After applying an aqueous coating composition on an object to be coated, the composition is cured. The aqueous coating composition contains a manganese oxide catalyst, activated carbon, a polyacrylate dispersant, and a resin, as well as a solvent mainly composed of water and a pH adjuster. The resin is at least one selected from a (meth)acrylic resin and a polyacrylic resin, and the manganese oxide catalyst is a manganese dioxide catalyst. The blending ratio of the manganese oxide catalyst to the activated carbon is 20 / 80≤activated carbon / manganese oxide catalyst≤50 / 50 in terms of mass ratio. The content of the polyacrylate dispersant is in the range of 2.6 to 43.1 parts by mass relative to 100 parts by mass of the total amount of the manganese oxide catalyst and the activated carbon. The polyacrylate dispersant has a weight average molecular weight in the range of 5000 to 30000, an acid value in the range of 1 to 50, and a hydrogen ion index in the range of pH 4 to pH 9.

Citation Information

Patent Citations

  • Cleaning ambient air by moving a vehicle with pollutant-treated surfaces through the atmosphere

    JP2002514966A

  • Air purification device for vehicle

    JP2014024027A

  • Image forming device

    JP1990273764A

  • Method for applying contaminant treatment composition to vehicle

    JP2008000746A